Postharvest biocontrol potential and mechanisms of Fusarium tricinctum against pear black spot caused by Alternaria alternata - Yun-Feng Liu; Zheng-Yu Zhu; Na Liu; Bo-Lin Li; Xue-Li He; Yu-Xing Zhang (Postharvest Biology and Technology, 2026)

Icaritin improves pregnancy outcomes in endometriosis by inhibiting ovarian granulosa cell senescence - Yalun He; Jie Ding; Yangshuo Li; Ji Sun; Cuiping Wei; Na Sun; Runnan Jiang; Ziming Zhao; Xiaolan Liang; Yiming Chen; Wen Cheng; Litai Zhang; et al. (Molecular Biology Reports, 2026)

IGFL2-AS1 is associated with poor prognosis in cervical cancer and promotes disease progression via the miR-126-5p/MACC1 axis - Zhibing Wu; Donglian Lan; Chao He; Na Li (Molecular Biology Reports, 2026)

Correction to: Gsα deficiency in macrophages promotes tumor progression via the MAPK signaling pathway - Wenjiang Yan; Jingjing Yang; Siyu Tan; Tixiao Wang; Rong Xiao; Na Li; Min Chen; Lee S. Weinstein; Lifan He; Chang Ma; Jingsu Zhang; Lifen Gao; et al. (Journal of Molecular Medicine, 2026)

Gsα deficiency in macrophages promotes tumor progression via the MAPK signaling pathway - Wenjiang Yan; Jingjing Yang; Siyu Tan; Tixiao Wang; Rong Xiao; Na Li; Min Chen; Lee S. Weinstein; Lifan He; Chang Ma; Jingsu Zhang; Lifen Gao; et al. (Journal of Molecular Medicine, 2026)

Decoding epigenetic drived heterosis in upland cotton (Gossypium hirsutum L.) through Multi-omics integration - Na Dong; Xiaoli Geng; Shoupu He; Zhen Peng; Hongge Li; Yuqing Li; Daowu Hu; Qinghua Yang; Xiaoping Pan; Xiongming Du; Qinglian Wang (Functional & Integrative Genomics, 2026)

Associations of prenatal per- and polyfluoroalkyl substance exposure with neonatal birth weight z-scores: The potential mediating role of maternal glucose homeostasis - Chun-Yong Wang; Zhen-Hua Li; Hai-Yang Weng; Xiao-Yu Zhao; Shao-Lei Pu; Meng-Na Zhu; Rui He; Xia-Juan Lu; Yu-Long Kan; Kai Huang; Guo-Peng Gao; Mao-Lin Chen; et al. (Environmental Pollution, 2026)

NIR-responsive mesoporous core-shell nanoplatform with oxygen self-supply and cascade targeting for reversing doxorubicin resistance via synergistic chemo-phototherapy - Yufeng Li; Yuping Jiang; Kexuan Wang; Xinyi Liu; Rui Yang; Lu Han; Tao He; Na Li; Da Huo (Chemical Engineering Journal, 2026)

CAMERA: A programmable CRISPR-gated logic system for high-fidelity assessment of Mycobacterium tuberculosis - Jiu Pu; Dan Bai; Yaoyi Zhang; Yiqi Zhang; Li Zhang; Yu He; You Wu; Na Yin; Zhe He; Shun Yao; Ting Xu; Yongchang Wu; et al. (Chemical Engineering Journal, 2026)

Fe(II)-driven abiotic-biotic relay alleviates denitrification bottleneck via chemical nitrite reduction and intracellular carbon - Na Hu; Qi Feng; Chenxi Li; Yuanyuan Liu; Baoli Zhu; Tianci Guo; Lei Tong; Jianbo Shi; Robert A. Sanford; Shuyi Li; Yu He; Yidan Hu; et al. (Water Research, 2026)

The transcription factor SbWRKY6 confers cadmium tolerance via activating SbPLAC8–17 expression in sorghum - Shan Cao; Jiqing Zhang; Zhengyu Guo; He Wang; Zengting Chen; Simin Li; Na Sui (Journal of Hazardous Materials, 2026)

Nature and timing of W-Sn mineralization in the Xin’anzi Deposit, Nanling Region: constraints from LA-ICP-MS cassiterite U-Pb geochronology and trace element composition - Gen-Wen He; Pei Ni; Wen-Sheng Li; Lin-Lin Peng; Gua-Hua Wang; Xin-Yue Liang; Jia-Hui Yan; Kai-Han Zhang; Li-Na Zhao (Journal of Asian Earth Sciences, 2026)

Inhibition of digestive enzymes with EGCG-loaded inverse alginate beads: a strategy for modulating starch digestion - Xiya Zhang; Jinling Zou; Shengju Ge; Xiaojing Li; Meng Li; Yang Qin; Man Li; Qingjie Sun; Jian He; Na Ji (Food Chemistry, 2026)

Zein-calcium alginate dual-shell liquid-core beads for tailored starch digestibility: Structural design, functional performance, and mechanistic analysis - Yang Qin; Xiya Zhang; Jinling Zou; Shengju Ge; Xiaojing Li; Man Li; Qingjie Sun; Qingze Han; Huanying Qin; Jian He; Na Ji (Food Chemistry, 2026)

Green synchronous fluorescence spectroscopy using non-carcinogenic standard: Rapid determination of carcinogenic polycyclic aromatic hydrocarbons in dairy products - Yi-Han Guo; Jia-Rong He; Jia-Wen Wei; Hong-Jun Liu; Jia-Lin Li; Ping-Ping Wu; Gaofeng Zheng; He-Dong Luo; Na Li; Yao-Qun Li (Food Control, 2026)

Efficient de novo biosynthesis of salidroside in Yarrowia lipolytica via integrated metabolic and glycosyltransferase engineering - Wen-Yan Tang; Xi-Yu Duan; Hu-Hu Liu; Chong Wang; Yue-Dong He; Hu Pan; Chang-Zhu Li; Xiang-Yang Lu; Xiao-Jun Ji; Yun Tian; Xiao-Na Yang (Bioresource Technology, 2026)

Effects of short-term continuous cropping on soil environmental factors and microbial communities of Pinellia ternata (Thunb.) Breit. - Guoli Wang; Yijia Zhao; Na Liu; Yu Tong; Wen Yin; Pan Li; Chunyu He; Yao Guo (Plant and Soil, 2026)

Nonlinear dynamics and optimal deployment of a deep-ocean mining riser with surface-mounted flow-disturbing robots - Shanfei Fan; Xiaoqiang Guo; Kelun Yang; Reza N. Jazar; Edson Denis Leonel; Nerguibaatar Tsend; Xianbin Liu; Yuwen Wang; Liming Dai; Jun Liu; Ning Zong; He Chen; et al. (Ocean Engineering, 2026)

Biotransformation of 2-Aminobenzothiazole by a newly isolated Rhodococcus sp. YQ-4 eliminates its toxicity to sensitive organisms - Fuyu Song; Jiaxi Liu; Qi Wu; Aiqin Diao; Yinhu Jiang; Xin Yan; Na Li; Jian He; Jiguo Qiu (International Biodeterioration & Biodegradation, 2026)

Simultaneous enantioselective determination of 30 chiral pesticides in vegetables: enantiomeric composition, separation, and absolute quantification using LC-MS/MS - Tianyue Zhao; Xin Jiang; Yingjie Zhu; Danning Shen; Chunzheng Li; Danli Liu; Hui Li; Yanqing Cao; Kun He; Na Wang (Food Chemistry, 2026)

Passive thermal regulation via radiative cooling enables efficient moisture sorption and electricity generation in heterostructured electrospun device - Na Li; Jiaqi Yang; Xiao Yu; Yimeng Ni; Jintao He; Dapeng Yang (Chemical Engineering Journal, 2026)

Salvianolic Acid A Relieves Acute Lung Injury by Promoting the Expression of FOXO1 and Activating Autophagy Through the Inhibition of miR-217-5p - Xia Liu; Yanping Shi; Li Huang; Hongbo Chen; Raofei Fan; Hongzhong Zhang; Qiaofen Li; Na Yan; Maiding He; Yonghua Yang (Biochemical Genetics, 2026)

Effects of GIAHS conservation on agricultural landscape and ecological sustainability in heritage sites: evidence from the Yuanyang Hani Rice Terraces - Jin-Rong Zhang; Hong-Bo Li; He-Ping Yang; Meng-Na Qi (Environment, Development and Sustainability, 2026)

Four new cytotoxic triterpenoids from Euphorbia fischeriana - Yuan-Biao He; Yan-Ni Ma; Yu-Ping Huang; Wen-Na Li; Ting-Xiang Shi; Jing Yang; Yong Zhao (Natural Product Research, 2026)

Selenomethionine antagonizes sodium arsenite-induced reproductive toxicity in zebrafish - Yan Zhang; Huan Wang; Xinru Bo; Yangfan Xu; Lingtian Xie; Yunyang Li; Jingli Mu; Jialing He; Na Zheng; Baoquan Zhao; Hongxing Chen; Wu Dong (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Detachable TMSD-CRISPR for programmable and highly specific discrimination of DNA/RNA mutations - Yiqi Zhang; Wang Luo; Yaoyi Zhang; Yu He; Li Zhang; You Wu; Kejia Wu; Hongyan Yu; Xiaole Han; Na Yin; Jiu Pu; Dan Bai; et al. (Chemical Engineering Journal, 2026)

Protective effects of melatonin on mouse ovarian tissue against oxidative stress and ferroptosis may involve the MT1 receptor - Sheng Nan Jiang; Xin Zhang; Li Na Si; Meng Wei; Xin Hui Wei; Yong Wei Wang; Tie Cheng Sun; Song He Yang; Zhi Hong Chen; Lu Yang Cheng (Cryobiology, 2026)

Dual covalent–hydrogen-bond networks enable synergistic thermo-mechanical performance and durability in polyimide films - Luling He; Xiong Li; Jiamei Liu; Yu Zhang; Na Song; Tongle Xu; Peng Ding (Chemical Engineering Journal, 2026)

Characterization of gluten quality of single-locus wheat lines with double null alleles at the Glu-1 locus - Shoufen Dai; Lingling Liang; Xiaorong Deng; Sisi Dong; Na Zhang; Chunmei He; Shiqi Luo; Jihao Chen; Fen Lu; Yapeng Li; Zixuan Fan; Bo Lu; et al. (Cereal Research Communications, 2026)

FTO-Mediated m6A Demethylation of MZF1 Regulates DECR1 to Promote Fatty Acid Oxidation and Exacerbate Myocardial Ischemia/Reperfusion Injury - Jin Tian; Qian He; Na Li; Yuehui Sun; Anxin Zhang; Haixiong Wang (Biochemical Genetics, 2026)

Post-earthquake road accessibility assessment in mountainous counties incorporating geological hazard density correction: A case study of Pingshan County, Hebei Province - Qiu-na Guo; He Zhang; Hong-yu Wang; Fan Yang; Jiang Li; Si-yu Liu (Applied Geophysics, 2026)

Engineering TadA8e-based base editors for GhWOX1 editing to create cotton with diverse leaf shapes - Guanying Wang; Shihe Jiang; Meijing Li; Yao He; Mingju Zhu; Fengjiao Hui; Li Yang; Jie Yu; Yongxue Hu; Mengqin Tang; Na Zhang; Bo Li; et al. (Science China Life Sciences, 2026)

Identification of novel genes involved in pediatric congenital heart disease using trio-based whole genome sequencing - Bo Wang; Mo Li; Wei Zhou; Huiwen Chen; Ying Xiang; Guocheng Shi; Guoling You; Luan Chen; Yesheng Zhang; Xiaoqing Zhang; Yunqian Gao; Lulu Li; et al. (Science Bulletin, 2026)

Impact of habitat biotic factors on selective food hoarding in Brandt's voles - Shan-shan Sun; Tao Liu; Hai-rui Yang; Zhi-liang Zhang; Ya-nan Li; Ming Ming; Hao-ting Zhang; Hai-wen Yan; Xin Li; Lin-lin Li; Na Zhu; Xiao-dong Wu; et al. (Journal of Arid Environments, 2026)

Organic fertilization alleviates soil sickness in monoculture systems by driving pathogen-suppressive rhizosphere community assembly - Tong Peng; Chuanji Zhang; Xiaoqi He; Zhenyu Cheng; Junjie Li; Yanfang Song; Ziyu Liu; Meiyun Pu; Yi Yan; Panshuai Fei; Yurong Bi; Xiaofan Na (Plant and Soil, 2026)

Bridging cortical intentions: brain–computer interfaces for spinal cord injury recovery - Xuantao Hu; Jiale He; Na Li; Jian Mo; Senyu Yao; Yubao Lu; Mudan Huang; Pan Jiang; Mao Pang; Lei He; Jin Gong; Zifeng Liu; et al. (Science Bulletin, 2026)

Asynchronous abrupt changes of lake ecosystems in the Anthropocene - Dinggui Wu; Tian Xia; Qingfeng Zhao; Yibin Sun; Na Song; Man Li; Tianchen He (Global and Planetary Change, 2026)

Functional trait variation of Rhododendron aureum in relation to Deyeuxia angustifolia encroachment in an alpine tundra - Na Li; Zhaoyong Hu; Guangqi Zhang; Mai-He Li; Zhengfang Wu; Renkai Dong; Suke Hou; Chao Song; Haibo Du (Plant and Soil, 2026)

Soil bacterial adaptation to plant invasion alters stoichiometric imbalances between soil microbes and resources in subtropical ecosystems - Meng Na; Shangqi Xu; Yong He; Tianyi Lu; Xiaoping Li; Jihai Zhou (Plant and Soil, 2026)

Distinct Gene Expression Patterns Reveal the Acclimatization Strategies To High-Salinity Stress in Gills of Mozambique Tilapia (Oreochromis mossambicus) - Jinghong He; Na Xue; Hancheng Bao; Boyuan Wang; Yuan Yao; Yun Li; Xin Qi; Qinfeng Gao; Yuan Tian (Marine Biotechnology, 2026)

Mobilization and redistribution of Arsenic during intense weathering of granite, eastern Tibetan Plateau, China - Zi-Han Xia; Jun-Wen Zhang; Na Wu; Mei-Li He; Qi Liu; Zhi-Qi Zhao (Environmental Geochemistry and Health, 2026)

Synergistic mechanism of hydrophobic and hydrophilic antioxidants in the interface of tree peony seed oil bilayer emulsion - Wen-Sen He; Na Wei; Jingyu Li; Qingzhi Wang; Haonan Yang; Chen Tan; Shouhe Huang; Huafang Ding; Jianhua Zhu; Hanyu Zhu; Zhen-Yu Chen (Food Chemistry, 2026)

Physiological and molecular responses to sodium acetate addition and supplementation in the two stages of Haematococcus pluvialis - Yanbin Li; Weizhao Han; Na Li; Tian Xie; Xin Tan; Song Tang; Yequan Sheng; Bangxiang He (Journal of Oceanology and Limnology, 2026)

Screening of quorum Sensing-Dependent strong promoters in Pseudomonas bijieensis 2P24 for metabolic optimization and Recombinant protein production - Jie Li; Hongguang Ma; Na Tai; Yue Fan; Mengxue Nie; Xuanying Tao; Zhilin Wang; Jinxin Wang; Xiangpeng Deng; Cheng Shen; Xuanxuan Chen; Jin Wang; et al. (World Journal of Microbiology and Biotechnology, 2026)

Prediction of surface settlement during shield tunnel boring based on variational mold decomposition and machine learning models - Na He; Pengfei Li; Mingju Zhang; Chenhe Ge (Tunnelling and Underground Space Technology, 2026)

The multi-carboxyl metal-organic framework MIL-101(Fe) effectively adsorbs total purines from whole soybean seeds - Deshuai Shao; Cui He; Na Li; Yuqing Gao; Xiaoyu Hu; Yingrun Cai; Qinqin Zhang; Jiahui Yao; Shuo Wang; Yifan Yang; Jiayi Pan; Huihui Gao; et al. (Food Chemistry, 2026)

Unveiling the genetic architecture of stripe rust resistance in wheat: a region-specific GWAS in Xinjiang, China - Feifei Zhang; Rong Wang; Wenjuan Jiao; Wanlong He; Yuzhe Zhang; Na Sun; Bin Bai; Kemei Li; Yukun Cheng; Hongwei Geng (Theoretical and Applied Genetics, 2026)

Synthesis of redox-responsive polyurethane nanocapsules for small-molecule delivery and antitumor evaluation on human leukemia K562 cells - Na Shi; Mengting Liu; Dandan He; Nianlin Feng; Yi Zhang; Dandan Liu; Chenchen Li; Zhenchao Wang (Molecular Diversity, 2026)

Estuarine plumes: Modulators of dissolved organic matter molecular signatures and biogeochemical fate in coastal ecosystems - Guodong Sun; Na Wang; Wenbo Wang; Yihui Guo; Juan Xu; Zijia Zeng; Penghui Du; Penghui Li; Chen He; Quan Shi; Dongxiao Wang; Wei Xie (Marine Pollution Bulletin, 2026)

Comprehensive analysis of metabolic response in Arabidopsis thaliana under heavy metal stress by mass spectrometry - Zhongyan Zhou; Donghao Li; Na Wang; Xiujuan Hong; Wen Su; Cheng Guo; Chongsheng He; Lei Yue (Journal of Hazardous Materials, 2026)

Development and validation of a multiplex high-risk HPV detection method using lyophilized microsphere technology and multicolor melting curve analysis - Miao Fu; Huabin Wang; Yingchao Wu; Chaoyong He; Wei Chen; Na Zhang; Xin Chen; Jinhua Wang; Xiaohuan Zhao; Meili Lin; SiSi Mao; Xi Xiang; et al. (Chemical Engineering Journal, 2026)

Bioorthogonally activatable methylene blue platform for selective prodrug activation and fluorescent imaging in living systems - Linlin Yang; Shiqiong Bai; Yuqing Nie; Yixuan Li; Fei Xin; Panpan Song; Na Gao; Liguo Ji; Lili Li; Guangjie He (Analytica Chimica Acta, 2026)

Regulated cell death in endometrial diseases: from molecular mechanisms to targeted therapies - Duo Zi; Jing Sun; Na Zuo; Tingting Li; Junzhi Liang; Jia Hu; Zhijing Na; Hao Zhang; Lixia He; Da Li (Archives of Toxicology, 2026)

High-humidity hot air impingement blanching (HHAIB): A novel strategy to reconcile drying efficiency and quality preservation in edible cricket processing - Jiaxin He; Xiaotong Fan; Lei Li; Shenyuan Quan; Shiye Luo; Jiabao Ni; Yanxiang Bi; Na Li; Ruge Cao; Xiaoming Fang (Food Chemistry, 2025)

Unveiling the binding landscape of cinnamaldehyde with digestive proteases:An exploration of specific interactions and conformational dynamics - Yi He; Po Chen; Lijuan Chen; Wei Wang; Jingtao Pang; Yilin Li; Na Gan; Di Wu (Food Chemistry, 2025)

S-regulated P-doping in hard carbon: Achieving “interlayer-adsorption-dominated” high-rate sodium storage - Weiyan Huang; Gang He; HaoGuang Lin; Feiming Tan; Na Li; Shaoming Huang (Chemical Engineering Journal, 2025)

Genetic structure analysis of a newly discovered wild population of Pontastacus leptodactylus in Xinjiang, China, based on the mitochondrial COI gene - Bin Li; Haorui Wang; Haini Shi; Qi Zhao; Shuxian Li; Adelijiang Wusiman; Maimaiti Aizizi; Ming He; Kefa Zhang; Yang Zhang; Na Li (Molecular Biology Reports, 2025)

Comparison of Lycium barbarum and Chenopodium glaucum litter decomposition reveals differential impacts on fusarium abundance and microbial community structure under field conditions - Chuanji Zhang; Zhenyu Cheng; Xiaoqi He; Meiyun Pu; Junjie Li; Ziyu Liu; Xiaomin Wang; Yurong Bi; Liguang Wang; Xiaofan Na (Applied Soil Ecology, 2025)

Elucidating the material basis and therapeutic mechanisms of Shaoma Zhijing granules for tourette syndrome by UPLC/Q-TOF-MS and multiple models - Qian Zhao; Xin-Xin Xu; Jin-Na Yang; Li-Juan Pei; Zhou-Yi Xie; Wen-Jia Wang; Jing-Xuan Fu; Zhao-Hui Song; He Sun; Kai-Jing Yan; Hui Wang; Yun-Hui Hu (Metabolic Brain Disease, 2025)

Development and validation of 10 K liquid chip for Inner Mongolia cashmere goat - Qi Xu; Haijiao Xi; Dongmei Shen; Tao Zhang; Jinquan Li; Rui Su; Qi Lv; Yanjun Zhang; Ruijun Wang; Na Wang; Baichuan Liu; Dong He; et al. (Small Ruminant Research, 2025)

Assessment of coffee endophytic yeasts for efficient mucilage removal and consistent quality improvement in coffee production - Yukai Suo; Na Yang; Hongmin Yang; Liping Li; Zhiyan Lan; Weiguang Wang; Feifei He; Shiwen Qin (Food Chemistry, 2025)

Enabling fast ion conduction at both interface and bulk for low-temperature quasi-solid-state batteries via fluorinated weak-solvent additives - Fangrun He; Zhaoxu Qiu; Naikuan Zhang; Na Li (Chemical Engineering Journal, 2025)

Effects of selenium–cadmium interactions on soil cadmium forms and the enrichment of selenium and cadmium in rice - Tianyi Lu; Yong He; Yanmei Ai; Meng Na; Shangqi Xu; Kun Cheng; Daming Li; Jihai Zhou (Plant and Soil, 2025)

Jaagichlorella menglunensis sp. nov. (Watanabeales, Chlorophyta), a new coccoid green alga isolated from China - Huiyin Song; Rongli Guan; Tian He; Langyue Zhang; Tiantian Li; Junfei Zhou; Yuxin Hu; Shuyin Li; Feng Liu; Lun Li; Na Zhang; Huafeng Xiao; et al. (Journal of Oceanology and Limnology, 2025)

Transcriptome Profiling Across Multiple Organs Unveils Potential Regulatory Effects of C-Fibers on Host in Mice - Yu He; Changgen Li; Jianhua Wei; Zhongying Yang; Luo Ren; Yu Deng; Na Zang; Enmei Liu (Journal of Molecular Neuroscience, 2025)

A multifunctional wearable patch based on hydrogel for strain sensing and epidermal sweat-analyzing - Shihao Wu; Jingwei Lu; Hongxiao Gao; Yuemeng Yang; Na He; Gan Miao; Li-Ping Xu (Chemical Engineering Journal, 2025)

Polystyrene microplastic pollution induces species-specific shifts in root traits and rhizosphere conditions in a temperate forest - Yingtong Zhou; Wei Guo; Ivano Brunner; Jiaxin Liu; Xiaoyue Na; Qinrong Tang; Junni Wang; Cunguo Wang; Mai-He Li (Journal of Hazardous Materials, 2025)

Constructing nitrogen-doped porous organic polymer- supported single-atom cobalt catalysts for highly efficient hydroformylation of internal olefins - Yuqing Wang; Miao Jiang; Na Liu; Tian Tian; Changdao Li; Zhao Sun; Gewen Yu; Yanming Wang; Wenxiu He; Jian Ding; Li Yan; Yunjie Ding (Chemical Engineering Journal, 2025)

A Co(III)-dipyrazolate framework for atmospheric CO2 photoreduction - Yingjie Wang; Xiang-Jing Kong; Guang-Rui Si; Tao He; Da-Yu Chen; Jian-Yu Zhang; Na Xing; A-Wu Zhou; Jian-Rong Li (Chemical Engineering Journal, 2025)

Deep soil moisture has limited impact on mitigating drought stress effects on plant transpiration in a subtropical secondary forest - Ji Zhang; Na Liu; Cicheng Zhang; Xinping Zhang; Xinguang He; Wulin Jiang; Jiajie Li; Ziwei Zhan; Dejing Peng; Dongjie Lv; Suixia Ni (Plant and Soil, 2025)

MSTC: a unified encoding method for geophysical big data retrieval - Henggao Geng; Suping Peng; Tao He; Na Xu; Zhangang Wang; Xianlei Xu; Xiaoqin Cui; Wenfeng Du; Yang Li; Kunheng Li (Earth Science Informatics, 2025)

Multiple Impacts of Climate Change and Anthropogenic Activities on Lacustrine Trophic State - Ge Xie; Yibo Zhang; Qing Wang; Kun Shi; Yunlin Zhang; Yongqiang Zhou; Boqiang Qin; Junliang He; Na Li (Global Change Biology, 2025)
The trophic state index (TSI) serves as a fundamental indicator for evaluating the water quality of lake ecosystems. Under climate change and human activities, global lake TSI has changed significantly, yet its response mechanisms remain unclear. To address this challenge, we developed a generalized TSI estimation model by integrating semi‐analytical algorithms with machine learning techniques, based on a comprehensive dataset comprising 3756 pairs of in situ measurements and remote sensing observations. The developed model demonstrated superior predictive performance with R 2 of 0.77 and RMSE of 8.25 for the testing dataset. Applying the model, we reconstructed a 21‐year time series (2003–2023) TSI for 14,189 global lakes with surface area ≥ 10 km 2 . The global mean TSI was estimated to be 54.07 ± 0.31. Among the lakes, 4.1% were classified as oligotrophic (TSI ≤ 38), 18.9% as mesotrophic (38 61). Globally, TSI showed a significantly increasing trend at a rate of 0.19 per decade ( p

Polystyrene bead ingestion promotes atherosclerosis plaque progression via BMP signaling in mice - Na Yang; Bo Wu; Xiaoxue He; Junhu Ma; Longhao Dai; RuiTing Ma; Tingting Yang; Xiaoxi Ning; Xiaoyan Li; Shaobin Jia (Food and Chemical Toxicology, 2025)

Breaking genetic linkage barriers to improve brown planthopper resistance and grain yield in japonica rice - Wenhui Wang; Jun He; Yunlong Wang; Na Li; Quanguang Sun; Menglong Zhang; Qi Li; Haosen Xu; Kun Shao; Shihao Zhang; Shijia Liu; Liangming Chen; et al. (Theoretical and Applied Genetics, 2025)

CD73 polymorphisms are associated with schizophrenia - He-Xia Peng; Li-Li Zhang; Dan Jiang; Na Jian; Ting-Mei Zhang; Jia-Guo Luo; Hai-Yan Yin (Purinergic Signalling, 2025)
Ecto-5’-nucleotidase/CD73 enzyme plays a key role in the regulation of extracellular adenosine levels, thereby exerting influence on adenosine homeostasis. Emerging evidence suggests that perturbations in purines and ecto-5’-nucleotidase activity are associated with an augmented susceptibility to schizophrenia. However, the precise impact of genetic variations in CD73 on individuals with schizophrenia remains poorly understood. Here, our study demonstrated that rs3734442 allele and rs4431401 heterozygote were conferred a significant risk of schizophrenia disease (rs3734442: odds ratio, 0.556; 95% CI, 0.375 to 0.825; p = 0.004; rs4431401: odds ratio, 1.881, 95% CI, 1.117 to 3.166; p = 0.020). Comparing different genders, we observed a significant association between rs3734442 genotypes and male cases (rs3734442: odds ratio, 0.452; 95% CI, 0.257 to 0.796; p = 0.007). Likewise, there was a significant association between rs4431401 genotypes and male patients (rs4431401: odds ratio, 2.570; 95% CI, 1.196 to 5.522; p = 0.015). Based on family history and antipsychotics medication usage, our data reveals that the rs9444348 allele exhibits the most significant association with familial susceptibility to schizophrenia (odds ratio, 1.541; 95% CI, 1.009 to 2.353; p = 0.048 for A vs G). Moreover, individuals carrying variants of rs6922, rs2229523, and rs2065114 while being treated with clozapine demonstrate a higher frequency proportion compared to those receiving risperidone treatment ( p = 0.035; p = 0.049; p = 0.027 respectively). Additionally, our results indicate that patients with GG genotype of rs9444348 had significantly higher likelihood of using clozapine instead of sulpiride ( p = 0.048). Overall, our data strongly suggest that genetic variations in CD73 are significantly associated with schizophrenia risk and may serve as valuable resources for identifying therapeutic targets.

Contrasting fungal community assembly mechanisms in bulk soil and rhizosphere of Torreya grandis across a 900-year age gradient - Bin Wang; Xiaofan Na; Shengyi Huang; Zhengcai Li; Zhichun Zhou; Juying Huang; Meiyun Pu; Zhenyu Cheng; Xiaoqi He (Plant and Soil, 2025)

Metabolome and Genome Analysis of a Novel Endophytic Fungus Aureobasidium pullulans KB3: Discovery of Polyketones and Polyketone Biosynthesis Pathway - Shuai Wang; Jia-Nuo He; Ying-Jie Wang; Wen-Ya Zhao; Qing-Xia Yang; Ya-Na Wang; Yang Zhang; Li-Ping Zhang; Hong-Wei Liu (Biochemical Genetics, 2025)

Combined genome and transcriptome provides insight into the genetic evolution of an edible halophyte Suaeda salsa adaptation to high salinity - Bing Cui; Ranran Liu; Qiong Yu; Jianrong Guo; Xihua Du; Zixin Chen; Chenyang Li; Tong Wang; Ru Liu; Rui He; Congcong Song; Yue Liu; et al. (Molecular Ecology, 2025)
Suaeda salsa L. is a typical halophyte with high value as a vegetable. Here, we report a 447.98 Mb, chromosomal‐level genome of S. salsa , assembled into nine pseudomolecules (contig N50 = 1.36 Mb) and annotated with 27,927 annotated protein‐coding genes. Most of the assembled S. salsa genome, 58.03%, consists of transposable elements. Some gene families including HKT1 , NHX , SOS and CASP related to salt resistance were significantly amplified. We also observed expansion of genes encoding protein that bind the trace elements Zn, Fe, Cu and Mn, and genes related to flavonoid and α‐linolenic acid metabolism. Many expanded genes were significantly up‐regulated under salinity, which might have contributed to the acquisition of salt tolerance in S. salsa . Transcriptomic data showed that high salinity markedly up‐regulated salt‐resistance related genes, compared to low salinity. Abundant metabolic pathways of secondary metabolites including flavonoid, unsaturated fatty acids and selenocompound were enriched, which indicates that the species is a nutrient‐rich vegetable. Particularly worth mentioning is that there was no significant difference in the numbers of cis ‐elements in the promoters of salt‐related and randomly selected genes in S. salsa when compared with Arabidopsis thaliana , which may affirm that plant salt tolerance is a quantitative rather than a qualitative trait in terms of promoter evolution. Our findings provide deep insight into the adaptation of halophytes to salinity from a genetic evolution perspective.

Multivariate model for predicting crop fluorine content based on soil physicochemical properties and fluorine speciation - Boxin Feng; Liming Gan; Qianni Men; Jiufen Liu; Yixin He; Na Guo; Tao He; Xiao Wang; Ronghua Li; Yajun Han (Environmental Monitoring and Assessment, 2025)

Flavor enhancement of soy protein isolate hydrolysates through the Maillard reaction and identification of saltiness-enhancing peptides - Hongbo Yi; Jun Li; Peng Wang; Shengnan Wang; Xiaofei Guo; Danshi Zhu; He Liu; Na Zhang (Food Bioscience, 2025)

UV-B stress reshapes root-associated microbial communities and networks, driven by host plant resistance - Chuanji Zhang; Na Gao; Xiaofan Na; Kaile Li; Meiyun Pu; Hao Sun; Yanfang Song; Tong Peng; Panshuai Fei; Junjie Li; Zhenyu Cheng; Xiaoqi He; et al. (Soil Biology and Biochemistry, 2025)

Effects of alkali and alkaline earth metals in biomass on co-pyrolysis characteristics and product distribution of coal and biomass - Na Liu; He Huang; Jun Feng; Rui Li; Xueli Huang; Yulong Wu (Fuel, 2025)

Enhanced pH-universal hydrogen evolution reactions on the Rh/MoO3 electrocatalysts - Jiaxin Yuan; Jianrui Feng; Gang Li; Yinghao Song; Na Yu; Xi Chen; Guanjie He; Yeshu Tan; Meng Ni (Chemical Engineering Journal, 2025)

Chemical constituents of Ainsliaea fragrans and their chemotaxonomic significance - Xiao-Ting He; Yun-Na Wang; Xue-Mei Zhou; Jing-Jing Zhang; Xiao-Li Li; Wei-Lie Xiao (Biochemical Systematics and Ecology, 2025)

Effects of homogenization and heat treatment on camel milk: Physicochemical properties, microstructure, and digestibility in infants - Na Su; Li Yi; Naihui Wang; Jing He; Liang Ming; Rendalai Si; Jiayu Zhang; Rimutu Ji (International Dairy Journal, 2025)

Polyhalogenated carbazoles contamination in East China Sea sediments: Spatial distribution, source apportionment, and ecological risk assessment - Li-Xin Kou; Xiao-Yu Zhang; Zi-Cen Zuo; Na Liu; Zhen He; Gui-Peng Yang (Environmental Research, 2025)

Oxidative Stress-mediated Loss of Hippocampal Parvalbumin Interneurons Contributes to Memory Precision Decline After Acute Sleep Deprivation - Yu-zhu Gao; Kai Liu; Xin-miao Wu; Cui-na Shi; Qiu-li He; Hai-peng Wu; Jian-jun Yang; Hao Yao; Mu-huo Ji (Molecular Neurobiology, 2025)

Subgrade cumulative deformation probabilistic prediction method based on machine learning - Zhixing Deng; Linrong Xu; Yongwei Li; Yunhao Chen; Na Su; Yuanxingzi He (Soil Dynamics and Earthquake Engineering, 2025)

Identification and validation of a major QTL, QFhb-6AL, for Fusarium head blight resistance on chromosome 6AL in wheat - Zhenzhen Zhu; Xuecheng Zhu; Na Zhang; Wenxi Wang; Jilu Liu; Fuping Zhang; Xiaomeng Ren; Yanpeng Ding; Fangyao Sun; Xi He; Sijia Hu; Xiuhua Li; et al. (Theoretical and Applied Genetics, 2025)

A PRA-Rab trafficking machinery modulates NLR immune receptor plasma membrane microdomain anchoring and blast resistance in rice - Di Liang; Dongyong Yang; Tai Li; Zhe Zhu; Bingxiao Yan; Yang He; Xiaoyuan Li; Keran Zhai; Jiyun Liu; Yoji Kawano; Yiwen Deng; Xu Na Wu; et al. (Science Bulletin, 2025)

Single- and combined-heavy metals/metalloids exposures are associated with infertility in US women aged 20–44: NHANES 2013–2020 analysis - He-Bin Chi; Jia-Jia Tang; Xiao-Yuan Fan; Han-Wen Zhang; Feng Tang; Xian-Shu Lin; Bing-Rui Yang; Na Li; Jun Guo; Li-An-Sheng Wu; Qiu-Qi Huang; Yin-Yin Xia (Reproductive Toxicology, 2025)

Microcarrier stiffness controls human amniotic epithelial cells (hAECs) proliferation and epithelial-mesenchymal transition (EMT) via remodeling ECM and Wnt/β-catenin pathway - Jia Tian; Wangping Hao; Juan Li; Xiangming Na; Shuang Wang; Wei Wei; Yuefeng Lu; Yangyang Cui; Wencheng Zhang; Zhiying He; Guanghui Ma; Weiqing Zhou (Chemical Engineering Journal, 2025)

A ratiometric electrochemical aptasensor for Ochratoxin A detection based on electroactive Cu-MOF and DNA conjugates resembling the structure of Bidens pilosa - Donghao He; Na Dong; Yuye Li; Dong Liu; Tianyan You (Analytica Chimica Acta, 2025)

T-2 toxin triggers immunotoxic effects in goats by inducing ferroptosis and neutrophil extracellular traps - Jing Huang; Kaifeng He; Xin Guo; Jiaxuan Wang; Han Hu; Xuhui Zhang; Na Guo; Yiwen Wang; Wenlong Huang; Rongsheng Huang; Tingting Liu; Xi Jiang; et al. (Toxicology and Applied Pharmacology, 2025)

Association between maternal serum zinc and birth weight is modified by neonatal SOD2 polymorphism and promoter methylation - Yuting Zeng; Yalong Wang; Yanan He; Qinyang Li; Ruiqin Chen; Cuiping Wu; Na Li; Xinya Cheng; Yuhui Du; Fangfang Yu; Yue Ba; Guoyu Zhou (Journal of Trace Elements in Medicine and Biology, 2025)

Characterization of the effects of bridging linker on the β-Lactoglobulin binding mechanism on the nanoscale metal-organic frameworks - Na Gan; Yali Song; Yilin Li; Peiran Liu; Si Chen; Yi He; Tingting Zeng; Wei Wang; Di Wu (Food Chemistry, 2025)

Novel one-step method to construct gellan gum-zein core-shell structured starch beads for regulating starch digestion - Zhiwei Lin; Weixian Li; Chengcheng Zhang; Linjie Zhan; Xiaoyang He; Yang Qin; Qingjie Sun; Na Ji (Food Chemistry, 2025)

Engineering a circular DNA agonist to activate MET signaling for promoting angiogenesis and regeneration of diabetic ulcer - Jun Zhu; Meixia Wang; Zhu Li; Ceheng Liao; Yangbing Li; Zhixi Duan; Xinxin Zhang; Yizhi Zhang; Fang He; Zhou Nie; Hong-Hui Wang; Na Cai; et al. (Chemical Engineering Journal, 2025)

Tauroursodeoxycholic acid targets HSP90 to promote protein homeostasis and extends healthy lifespan - Jia-Yu Liu; Yao Wang; Yue Guo; Run-Qi Zheng; Yun-Ying Wang; Yan-Yan Shen; Yan-Hong Liu; Ai-Ping Cao; Rui-Bo Wang; Bo-Yang Xie; Shuai Jiang; Qiu-Ying Han; et al. (Science China Life Sciences, 2025)

ALFIN-like proteins link histone H3K4me3 to H2A ubiquitination and coordinate diverse chromatin modifications in Arabidopsis - Xiao-Min Su; Dan-Yang Yuan; Na Liu; Zhao-Chen Zhang; Minqi Yang; Lin Li; She Chen; Yue Zhou; Xin-Jian He (Molecular Plant, 2025)

A Se-hyperaccumulating plant Cardamine violifolia: From its nutritional value to potential applications in foods - Li Wang; Shuyi Li; Feifei Wang; Na Zhang; Xu Chen; Xuehua Wang; Jiangling He; Chen Cheng; Zhenzhou Zhu (Trends in Food Science & Technology, 2024)

An optimised molecular-based method for ecological study of tardigrades in soils - Zi-Yang He; Hang-Wei Hu; Keren Wu; Li Bi; Shuo Na; Anthony Weatherley; Michael Nash; Ji-Zheng He (Soil Biology and Biochemistry, 2024)

Exogenous silicon facilitates safe crop production in cadmium-contaminated soils: A comprehensive meta-analysis - Hongjie Liu; Li Chen; Xiaohan Bai; Na Wang; Qingliang Cui; Ji Liu; Roland Bol; Tianyi Qiu; Yuxia Mei; Haoran He; Shiqi Bian; Nan Chang; et al. (Journal of Hazardous Materials, 2024)

Intimate microbe-water-mineral interactions mediate alkalization in the pyroxene-rich iron ore mines in Panxi area, Southwest China - Yu He; Yongzhe Li; Yue Pan; Jianying Shang; Weimin Sun; Meng Wang; Hao Fan; Robert A. Sanford; Na Wei; Shuming Peng; Daihong Xie; Weiguang Zhang; et al. (Journal of Hazardous Materials, 2024)

Identification of novel salt-enhancing peptides in soy protein and molecular docking studies with transmembrane channel-like 4 (TMC4) - Jun Li; Peng Wang; Hongbo Yi; Shengnan Wang; He Liu; Na Zhang (Food Bioscience, 2024)

Ru induced charge redistribution of MnO2 spheric nanozyme boosted hydrogen sulfide selective detection and cystathionine γ-lyase activity sensitive evaluation - Zhao Li; Xuan Zhang; Haorong Cheng; Zhongyuan Gu; Changchun He; Ju Wang; Xinxin Shi; Weidan Na; Tongxiang Li; Lin Tian (Chemical Engineering Journal, 2024)

PXMP4 promotes gastric cancer cell epithelial-mesenchymal transition via the PI3K/AKT signaling pathway - Wei Li; Xiangyang Dong; Zhidan Wan; Wenxin Wang; Jingyu Zhang; Yongrun Mi; Ruiyuan Li; Zishan Xu; Beixi Wang; Na Li; Guoyang He (Molecular Biology Reports, 2024)

Unveiling the impacts of microplastic pollution on soil health: A comprehensive review - Nan Chang; Li Chen; Na Wang; Qingliang Cui; Tianyi Qiu; Shuling Zhao; Haoran He; Yi Zeng; Wei Dai; Chengjiao Duan; Linchuan Fang (Science of The Total Environment, 2024)

Drinking water safety improvement and future challenge of lakes and reservoirs - Yunlin Zhang; Jianming Deng; Yongqiang Zhou; Yibo Zhang; Boqiang Qin; Chunqiao Song; Kun Shi; Guangwei Zhu; Xuejiao Hou; Yinjun Zhang; Shiwen He; R. Iestyn Woolway; et al. (Science Bulletin, 2024)

Season-dependent climate sensitivity of the surface runoff of major rivers in Changbai Mountain - Xinran Li; Hong S. He; Na Li; Heyuan Yu; Shengwei Zong; Zhengfang Wu; Haibo Du (Journal of Hydrology, 2024)

Acne-related UVA-induced facial fluorescence: An exploratory study from physiological properties to tissue structure information - Xing Ren; Yanan Sun; Yuxin Zhang; Na Zhou; Yunong Wang; Lishuang Li; Xinyu Gao; Yuman Ma; Xianyu Li; Zhe Shu; Honghui He; Yi Wang (Journal of Photochemistry and Photobiology B: Biology, 2024)

Excitotoxic Storms of Ischemic Stroke: A Non-neuronal Perspective - Xiao-man Yang; Hao Yu; Jia-xin Li; Na Li; Chong Li; Dong-han Xu; Hao Zhang; Tian-he Fang; Shi-jun Wang; Pei-yu Yan; Bing-bing Han (Molecular Neurobiology, 2024)

NUS1 Variants Cause Lennox-Gastaut Syndrome Related to Unfolded Protein Reaction Activation - Nan-Xiang Shen; Xiao-Chong Qu; Jing Yu; Cui-Xia Fan; Fu-Li Min; Ling-Ying Li; Ming-Rui Zhang; Bing-Mei Li; Jie Wang; Na He; Wei-Ping Liao; Yi-Wu Shi; et al. (Molecular Neurobiology, 2024)

Encapsulation hierarchical bimetallic oxide with flexible electrospinning carbon nanofibers for efficient capacitive deionization - Ming Gao; Na Li; Caiqing He; Yuchen Kang; Hao Kong; Li Yang; Wencui Liang; Tianqi Ao; Haiyan Mou; Wenqing Chen (Desalination, 2024)

Magnesium hexacyanoferrate nanocatalysts alleviates fibromyalgia syndrome by reversing cellular ferroptosis - Ling Jiang; Zhongqiang Zhu; Kun Han; Dongxu Chen; Lu Huang; Na Hu; Jiayi Du; Bowen Zhang; Yi Su; Tao Li; Xiangyi Ren; Xiang He (Chemical Engineering Journal, 2024)

Adsorption behavior and mechanism of different types of (aged) microplastics for napropamide in soils - Qing Wang; Wenjie Ge; Renyong Shi; Jian He; Shuchang Li; Changqing Zhu; Xiaohui Zhang; Mali Shi; Ni Ni; Na Wang (Chemosphere, 2024)

The monokaryotic filamentous fungus Ustilago sp. HFJ311 promotes plant growth and reduces Cd accumulation by enhancing Fe transportation and auxin biosynthesis - Shengwang Wang; Xiaofan Na; Meiyun Pu; Yanfang Song; Junjie Li; Kaile Li; Zhenyu Cheng; Xiaoqi He; Chuanji Zhang; Cuifang Liang; Xiaomin Wang; Yurong Bi (Journal of Hazardous Materials, 2024)

Biochar with KMnO4-hematite modification promoted foxtail millet growth by alleviating soil Cd and Zn biotoxicity - Xirui Kang; Na Geng; Yaping Li; Wei He; Hui Wang; Hong Pan; Quangang Yang; Zhongchen Yang; Yajie Sun; Yanhong Lou; Yuping Zhuge (Journal of Hazardous Materials, 2024)

High Magnesium Promotes the Recovery of Binocular Vision from Amblyopia via TRPM7 - Menghan Dai; Jie Li; Xiangwen Hao; Na Li; Mingfang Zheng; Miao He; Yu Gu (Neuroscience Bulletin, 2024)

Performance of pharmaceutical products removal in a bioelectrochemical system at low temperatures and changes in microbial communities and antibiotic resistance genes - Mei Wu; Nuerla Ailijiang; Na Li; Abudoushalamu Zaimire; Hailiang Chen; Chaoyue He; Yiming Zhang (Environmental Science and Pollution Research, 2024)

Association between residential greenness and incident delirium: A prospective cohort study in the UK Biobank - Qida He; Mengtong Sun; Yu Wang; Guoxian Li; Hanqing Zhao; Ze Ma; Zhaolong Feng; Tongxing Li; Qiang Han; Na Sun; Linyan Li; Yueping Shen (Science of The Total Environment, 2024)

Bio-inspired gradient poly(lactic acid) nanofibers for active capturing of PM0.3 and real-time respiratory monitoring - Guiying Zhu; Cunmin Wang; Ting Yang; Na Gao; Yifan Zhang; Jintuo Zhu; Xinjian He; Jiang Shao; Shihang Li; Mingming Zhang; Shenghui Zhang; Jiefeng Gao; et al. (Journal of Hazardous Materials, 2024)

Regional uncertainty analysis between crop phenology model structures and optimal parameters - Chenyao Yang; Na Lei; Christoph Menz; Andrej Ceglar; Jairo Arturo Torres-Matallana; Siqi Li; Yanling Jiang; Xianming Tan; Lei Tao; Fang He; Shigui Li; Bing Liu; et al. (Agricultural and Forest Meteorology, 2024)

Ultra-trace Ag doped carbon quantum dots with peroxidase-like activity for the colorimetric detection of glucose - Wei Tan; Guixiang Yao; Hang Yu; Yanzhi He; Mingrong Lu; Tianru Zou; Xiaopei Li; Pengyuan Yin; Pei Na; Wenrong Yang; Min Yang; Hongbin Wang (Food Chemistry, 2024)

Carbon nanotube incorporated quaternized lignin-based loose nanofiltration membrane toward dye/salt separation - Zhenyu He; Na Zhang; Li Zhao; Zhenghua Li; Wanling Cui; Yuangang Zhu; Yi Wang; Huining Deng; Chengrun Si; Wen Bo; Jie Zhou; Shicai Xu; et al. (Journal of Environmental Chemical Engineering, 2024)

Short-time potentiostatic assisted borate to induce the generation of ultrathin NiFe LDH active phase for industrial-level water oxidation - Yu Ma; Jia-Jun Wang; Xiao-Han Liu; Na Xu; Xin Li; You-He Wang; Lian-Ming Zhao; Yong-Ming Chai; Bin Dong (Chemical Engineering Journal, 2024)

Delaying crystallization and anchoring the grain boundaries defects via π-π stacked molecules for efficient and stable wide-bandgap perovskite solar cells - Jinliang Shen; Na Li; Yuhang Wang; Xiang Ge; Junlei Tao; Song Yin; Xingkun Ning; Tingwei He; Guangsheng Fu; Shaopeng Yang (Chemical Engineering Journal, 2024)

Delineating cathodic extracellular electron transfer pathways in microbial electrosynthesis: Modulation of polarized potential and Pt@C addition - Yue Wang; Siyang Yu; Xue Zheng; Xiaobing Wu; Ying Pu; Gaoying Wu; Na Chu; Xiaohong He; Daping Li; Raymond Jianxiong Zeng; Yong Jiang (Bioresource Technology, 2024)

Non-negligible impact of microplastics on wetland ecosystems - Na-ying Li; Bo Zhong; Yun Guo; Xian-xiang Li; Zao Yang; Yi-xin He (Science of The Total Environment, 2024)

Sublethal effect and detoxifying metabolism of metaflumizone and indoxacarb on the fall armyworm, Spodoptera frugiperda - Li Zhang; Hui-Zi Wu; Pei-Yun He; Hai-Qun Cao; Wan-Na Zhang; Ying-Chuan Peng; Cheng-Wang Sheng (Pesticide Biochemistry and Physiology, 2024)

Summer heatwaves promote harmful algal blooms in the Fuchunjiang Reservoir, an important drinking water source - Shiwen He; Yunlin Zhang; Na Li; Kun Shi; Yibo Zhang; Boqiang Qin; Guangwei Zhu; Mingliang Liu; Keqiang Shao (Journal of Environmental Management, 2024)

Identification and molecular docking of a novel antidiabetic peptide from protamex-camel milk protein hydrolysates against α-amylase and DPP-IV - Na Su; Li Yi; Jing He; Liang Ming; Tuyatsetseg Jambal; Batmunkh Mijiddorj; B. Maizul; Ts. Enkhtuul; Rimutu Ji (International Dairy Journal, 2024)

Spatial-temporal constraints for surface soil moisture mapping using Sentinel-1 and Sentinel-2 data over agricultural regions - ZHOU Ya'nan; WANG Binyao; ZHU Weiwei; FENG Li; HE Qisheng; ZHANG Xin; WU Tianjun; YAN Na'na (Computers and Electronics in Agriculture, 2024)

The diversity of planktonic bacteria driven by environmental factors in different mariculture areas in the East China Sea - Wei Liu; Yanlin Bao; Kejun Li; Na Yang; Peimin He; Chiquan He; Jinlin Liu (Marine Pollution Bulletin, 2024)

Mechanical properties and constitutive model of high-abundance methane hydrates containing clayey–silt sediments - Fan Yang; Changjun Li; Na Wei; Wenlong Jia; Jie He; Shuoshuo Song; Yuanrui Zhang; Youzhi Lin (Ocean Engineering, 2024)

Copper nanoparticles encapsulated in zeolite 13X for highly selective hydrogenation of CO2 to methanol - Yingnan Li; Tao Du; Chuang Chen; He Jia; Jingchao Sun; Xin Fang; Yisong Wang; Hongming Na (Journal of Environmental Chemical Engineering, 2024)

The impact of volatiles on tick-host interaction and vector competence - Ming-Zhu Zhang; Juan Wang; Li-Feng Du; Pei-Jun He; Na Jia (Current Opinion in Insect Science, 2024)

Engineering yeast to convert lignocellulose into vanillin - Xin Xin; Ren-Kuan Zhang; Shi-Chang Liu; Zi-Jing He; Ruo-Ying Liu; Hai-Na Lan; Zhi-Hua Liu; Bing-Zhi Li; Ying-Jin Yuan (Chemical Engineering Journal, 2024)

Experimental investigation on pillar rockburst of true triaxial four-face rapid unloading under high stress - Jieyu Li; Dongqiao Liu; Manchao He; Yunpeng Guo; Na Li; Jiamiao Zhang (Bulletin of Engineering Geology and the Environment, 2024)

Corrigendum to “Temporal assembly patterns of microbial communities in three parallel bioreactors treating low-concentration coking wastewater with differing carbon source concentrations” [Journal of Environmental Sciences, Volume 137, March 2024, Pages 455–468] - Weijia Li; Yu Xia; Na Li; Jie Chang; Jing Liu; Pei Wang; Xuwen He (Journal of Environmental Sciences, 2024)

Temporal assembly patterns of microbial communities in three parallel bioreactors treating low-concentration coking wastewater with differing carbon source concentrations - Weijia Li; Yu Xia; Na Li; Jie Chang; Jing Liu; Pei Wang; Xuwen He (Journal of Environmental Sciences, 2024)

In vitro digestion and fecal fermentation of encapsulated starch constructed via layer-by-layer coating of calcium alginate - Congli Cui; Mingju Li; Xiaoyang He; Na Ji; Yang Qin; Lei Dai; Liu Xiong; Qingjie Sun (Food Hydrocolloids, 2024)

Common vetch intercropping with reduced irrigation ensures potato production by optimizing microbial interactions - Ting Che; Xinyue Zhang; Mingyue He; Fei Wang; Na Li; Xiayun Zang; Zhuoliang Xiao; Yuanzhou Xu; Feng Hu; Yongfeng Ren; Huijuan Zhang; Li Xu; et al. (Field Crops Research, 2024)

Norepinephrine-induced hydrophilic Pd aerogels with photothermal-boosted multienzyme-like activity for chemodynamic therapy of MRSA infections - Minghui Wang; Na Li; Nanyun Lin; Yingying Wu; Wei Zhou; Ximei Sun; Peixian Wu; Qian Fu; Wenjie Wang; Zheng Liu; Shuiyuan He; Mengyu Zhou; et al. (Chemical Engineering Journal, 2024)

Stochastic processes dominated the soil bacterial community assemblages along an altitudinal gradient in boreal forests - Li Ji; Song Sheng; Fangyuan Shen; Lili Yang; Shizhi Wen; Gongxiu He; Na Wang; Xu Wang; Lixue Yang (CATENA, 2024)

Short-term effects of exposure to ambient PM2.5 and its components on hospital admissions for threatened and spontaneous abortions: A multicity case-crossover study in China - Heng He; Na Wan; Zhenzhen Li; Zihan Zhang; Zesen Gao; Qingdan Liu; Xiaolei Ma; Yuqing Zhang; Rongxiang Li; Xiuhong Fu; Weihong Qiu (Chemosphere, 2024)

Mechanisms and targeted reversion/prevention of hepatic fibrosis caused by the non-hereditary toxicity of benzo(a)pyrene - Xinru Du; Ming Jin; Ruzhi Li; Fei Zhou; Yuanze Sun; Qinliang Mo; Sisi Song; Na Dong; Shuoke Duan; Maoxuan Li; Ming Lu; Chi Zhang; et al. (Science of The Total Environment, 2024)

Greenhouse gas emissions of municipal solid waste in Shanghai over the past 30 years: Dependent on the dynamic waste characteristics and treatment technologies - Xiaojing Li; Fan Lü; Nanlin Liao; Hua Zhang; Na Yang; Pinjing He (Resources, Conservation and Recycling, 2024)

Peroxisome Proliferator-Activated Receptor-γ Coactivator-1α in the Spotlight with Multiple Sclerosis - Ya-Na Yang; Mao-Qing Zhang; Feng-Lin Yu; Bing Han; Ming-Yue Bao; Yan He; Xing Li; Yuan Zhang (Neuroscience Bulletin, 2024)

Antioxidant analysis of flavonoids extracted from Artemisia argyi leaf and their antibacterial activities against food-borne pathogens Escherichia coli and Staphylococcus aureus - Zichao Wang; Xueyan Zhou; He Chang; Zhihan Shu; Haiqin Gou; Yi Zheng; Yanhui Yang; Yahui Yang; Qi Wang; Na Li (Biologia, 2024)

Soil rare microorganisms mediated the plant cadmium uptake: The central role of protists - Xingguo He; Xian Xiao; Weiwei Wei; Liangzhong Li; Yuan Zhao; Na Zhang; Mingyu Wang (Science of The Total Environment, 2024)

Activate the filtration capability of 3.5 nm ultra-large pores and eliminate the requirement of pore homogeneity for carbon nanotube array membranes - Na Li; Zemeng Feng; Yiyue He; Zhaogang Peng; Xiangrui Meng; Huijuan Lin; Kui Xu (Desalination, 2024)

Interfacial Mo-S bond-reinforced hierarchical S-scheme heterostructure of Bi2MoO6@ZnIn2S4 for highly-selective and efficient CO2 photoreduction into CO - Jiale He; Jie Lin; Yu Zhang; Yingfei Hu; Qingling Huang; Guobing Zhou; Wei Li; Jianqiang Hu; Na Hu; Zhen Yang (Chemical Engineering Journal, 2024)

Progression of an emission inventory of China integrating CO2 with air pollutants: A chance to learn the influence of development on emissions - Guorui Zhi; Jinhong Du; Aizhong Chen; Wenjing Jin; Na Ying; Zhihui Huang; Peng Xu; Di Wang; Jinghua Ma; Yuzhe Zhang; Jiabao Qu; Hao Zhang; et al. (Atmospheric Environment, 2024)

Observation of Arctic surface currents using data from a surface drifting buoy - Hongxia Chen; Lina Lin; Long Fan; Wangxiao Yang; Yinke Dou; Bingrui Li; Yan He; Bin Kong; Guangyu Zuo; Na Liu (Acta Oceanologica Sinica, 2024)

Kaempferol and ginsenoside Rg1 ameliorate acute hypobaric hypoxia induced lung injury based on network pharmacology analysis - Na Li; Yuan Cheng; Tao Jin; Lirui Cao; Jieyu Zha; Xiong Zhu; Qing He (Toxicology and Applied Pharmacology, 2023)

Functional characterization of four antenna-biased chemosensory proteins in Dioryctria abietella reveals a broadly tuned olfactory DabiCSP1 and its key residues in ligand-binding - Ning-Na Yin; Yu-Juan Yao; Yin-Lan Liang; Zheng-Quan Wang; Yong-He Li; Nai-Yong Liu (Pesticide Biochemistry and Physiology, 2023)

Three new flavones from the whole plants of Cassia auriculata Linn. and their antiviral activities - Rui-Feng Xiong; Jun-Na Zheng; Qing-Yang Wu; Ning Jiang; Yuan-Sheng He; Yong-Jun Zhang; Ben-Hui Li; Wei Li; Qiu-Fen Hu; Zhen-Yuan Xia; Yin-Ke Li (Phytochemistry Letters, 2023)

Revolutionizing material design for protonic ceramic fuel cells: Bridging the limitations of conventional experimental screening and machine learning methods - Idris Temitope Bello; Daqin Guan; Na Yu; Zheng Li; Yufei Song; Xi Chen; Siyuan Zhao; Qijiao He; Zongping Shao; Meng Ni (Chemical Engineering Journal, 2023)

Protocol for Brain Magnetic Resonance Imaging and Extraction of Imaging-Derived Phenotypes from the China Phenobank Project - Chengyan Wang; Zhang Shi; Yan Li; Xueqin Xia; Xutong Kuang; Shufang Qian; Le Xue; Lizhen Lan; Yudan Wu; Na Zhang; Ji Tao; Xumei Hu; et al. (Phenomics, 2023)

Simultaneous extraction of C3H8 and C2H6 from ternary C3H8/C2H6/CH4 mixtures in an ultra-microporous metal–organic framework - Lan Lan; Nan Lu; Jia-Cheng Yin; Qiang Gao; Feifan Lang; Ying-Hui Zhang; Hong-Xiang Nie; Na Li; Xian-He Bu (Chemical Engineering Journal, 2023)

Hydrogeochemical characterization and precursor anomalies of hot springs in the North Tianshan orogen - Zhihua Ding; Xiaocheng Zhou; Chengguo Wang; Jingchao Li; Miao He; Jiao Tian; Kayimu Saimaiernaji; Chengying Zhu; Wei Yan; Rong Ma; Xinyong Li; Na Li; et al. (Applied Geochemistry, 2023)

Stability of exogenous Cadmium in different vineyard soils and its effect on grape seedlings - Ajigul Mamut; Jianquan Huang; Okbagaber Andom; He Zhang; Na Zhang; Hu Zhou; Yizhong Lv; Zhaojun Li (Science of The Total Environment, 2023)

Adsorption mechanism of methylene blue by magnesium salt-modified lignite-based adsorbents - Ruzhan Bai; Yan Feng; Lei Wu; Na Li; Quansheng Liu; Yingyue Teng; Runxia He; Keduan Zhi; Huacong Zhou; Xueyan Qi (Journal of Environmental Management, 2023)

The coupling effects between acid-catalyzed hydrothermal pretreatment and acidic/alkaline deep eutectic solvent extraction for wheat straw fractionation - Na Pan; Baiheng Jiang; Jinguang Hu; Mei Huang; Jinsong He; Qin Jiang; Li Zhao; Fei Shen; Dong Tian (Bioresource Technology, 2023)

Observed and projected changes in wet and dry spells for the major river basins in East Asia - Lirong Huang; Haibo Du; Yongcai Dang; Hong S. He; Lei Wang; Risu Na; Na Li; Zhengfang Wu (International Journal of Climatology, 2023)
Spatiotemporal changes in wet and dry spells had significantly contributed to climate‐related natural hazards in East Asia, especially in river basins undergoing warming. However, few studies have systematically analysed these changes for river basins at different latitudes. Herein, we investigated the observed and projected variations in wet and dry spells for East Asian river basins at different latitudes. We found that river basins at low latitudes (Yangtze and Pearl rivers) had obvious wet characteristics, whereas those at high latitudes (Amur and Yellow rivers) had obvious dry characteristics. In general, the river basins presented a ‘wet south but dry north’ spatial pattern. Long‐duration wet spells have been shown to be the primary contributor to total wet spells in low‐latitude river basins, while long‐duration dry spells have been found to be the primary contributor to total dry spells in high‐latitude river basins. Importantly, climate is changing from prolonged wet spells to short, intense wet spells in low‐latitude river basins, whereas the climate is changing from single, short dry spells to moderate, prolonged dry spells at high latitudes. These changes indicate a high probability of flash floods in river basins at low latitudes and a high probability of droughts at high latitudes. In the future, more temporally clustered heavy precipitation events and prolonged dry spells may lead to increasingly uneven precipitation in high‐latitude river basins and the Pearl River basin, especially under the higher shared socioeconomic pathway scenarios. In contrast, more frequent consecutive heavy precipitation events may aggravate the risk of flooding in the Yangtze River basin. These findings are expected to serve as a guide for flood and drought risk mitigation in East Asia under a warming climate.

Interaction of metabolism-related pathway gene variants with bisphenol A exposure on serum lipid profiles - Heng He; Fuwei Zhang; Shuang Zhou; Shanshan Zhang; Lu Wang; Jiaoyuan Li; Qiang Zeng; Ying Zhu; Jianbo Tian; Jiang Chang; Liming Cheng; Qing Lu; et al. (Environmental Toxicology and Pharmacology, 2023)

Dynamic Measurements of Cerebral Blood Flow Responses to Cortical Spreading Depolarization in the Murine Endovascular Perforation Subarachnoid Hemorrhage Model - Jin Yan; Wenlang Li; Chao Zhou; Na Wu; Xiaomin Yang; Qiuling Pan; Tao He; Yue Wu; Zongduo Guo; Yongzhi Xia; Xiaochuan Sun; Chongjie Cheng (Translational Stroke Research, 2023)

Specific pupylation as IDEntity reporter (SPIDER) for the identification of protein-biomolecule interactions - He-Wei Jiang; Hong Chen; Yun-Xiao Zheng; Xue-Ning Wang; Qingfeng Meng; Jin Xie; Jiong Zhang; ChangSheng Zhang; Zhao-Wei Xu; Zi-Qing Chen; Lei Wang; Wei-Sha Kong; et al. (Science China Life Sciences, 2023)

Construction of a food-grade gene editing system based on CRISPR-Cas9 and its application in Lactococcus lactis NZ9000 - Yangping Zhou; Fei Song; Hongru Yang; Dongyao Li; Na Zhang; Kunlun Huang; Xiaoyun He; Miaoshu Wang; Hongtao Tian; Chen Li (Biotechnology Letters, 2023)

Influence of e-waste exposure on DNA damage and DNA methylation in people living near recycling sites - Na Li; Jinhan Wang; Kejun Li; Ping Yang; Yan Wang; Chang Xu; Ningning He; Kaihua Ji; Huijuan Song; Manman Zhang; Liqing Du; Qiang Liu (Environmental Science and Pollution Research, 2023)

Peroxydisulfate activation by CuFe2S3 nanocrystal doped C/N catalyst for phenanthrene degradation: Experimental, mechanism, and density functional theory calculation - Shaomeng Huang; Liping Wang; Qiongqiong He; Leilei Sun; Dan Li; Na Liu; Yaqin Zhao; Lei Yang (Chemical Engineering Journal, 2023)

Effects of dietary oat supplementation on carcass traits, muscle metabolites, amino acid profiles, and its association with meat quality of Small-tail Han sheep - Li-wei Wang; Shao-feng Su; Jie Zhao; Xiao-long He; Shao-yin Fu; Biao Wang; Yun-fei Wang; Da-qing Wang; Na-na Yun; Xin Chen; Damien P Belobrajdic; Terigele; et al. (Food Chemistry, 2023)

Effects of sericin on oxidative stress and PI3K/AKT/mTOR signal pathway in cryopreserved mice ovarian tissue - Wei Han Shu; Song He Yang; Meng Wei; Xiao Chao Liu; Zi Xuan Chen; Chen Yang Wei; Xin Zhang; Li Na Si; Zhi Hong Chen; Yue Bing Qiao; Dong Mei Li; Tie Cheng Sun; et al. (Cryobiology, 2023)

Effects of bisphenols on lipid metabolism and neuro–cardiovascular toxicity in marine medaka larvae - Xueyou Li; Xiaoxu He; Xiaona Lin; Weihao Li; Jiahao Gao; Ning Zhang; Yusong Guo; Zhongduo Wang; Na Zhao; Bo Zhang; Zhongdian Dong (Aquatic Toxicology, 2023)

Study on the inactivation and reactivation mechanism of pathogenic bacteria in aquaculture by UVC-LED - Weixiao Zhang; Ruipin Huang; Tao Zhang; Baolong Wang; Na Li; Yan Sun; He Ma; Qian Zhang; Junxin Zhang; Ying Liu (Frontiers in Marine Science, 2023)
Ultraviolet disinfection is an important method for controlling the large-scale outbreaks of diseases in aquaculture. As a novel and promising light source, ultraviolet light-emitting diode (UV-LED) has the advantages of safety, high efficiency and no environmental pollution risks. However, it remains unclear whether UV-LEDs can replace traditional UV light sources for aquaculture water treatment processes. Present study aimed to investigate the efficacy of UVC-LEDs (265 nm) on pathogenic bacteria, specifically Aeromonas salmonicida and Escherichia coli . The effects of UVC-LED dose, light conditions, and temperature on bacterial reactivation were also investigated. The results showed that exposure to UVC-LED effectively inactivated both types of bacteria. To achieve 4.5-log inactivation of A. salmonicida and E. coli , 24 mJ/cm 2 and 28 mJ/cm 2 UVC-LED irradiation were required, and the inactivation rate increased with increasing UVC-LED fluence. Both A. salmonicida and E. coli were revived after UVC-LED disinfection, and photoreactivation was significantly higher than dark reactivation. Bacterial reactivation rate due to high-dose UVC-LED treatment was significantly lower than that of low-dose. After 72 h of reactivation, photoreactivation and dark reactivation rates were 1 ± 0.4% and 2.2 ± 0.2%for A. salmonicida , and 0.02% and 0% for E. coli , respectively. Besides, the photoreactivation rates for the two bacteria exhibited different correlations with temperature. The highest photoreactivation rate for A. salmonicida was 68.7 ± 4% at 20°C, while the highest photoreactivation rate for E. coli was 53.98 ± 2.9% at 15°C for 48 h. This study reveals the rapid and efficient inactivation of bacteria by UVC-LED, and elucidates the mechanism and influencing factors for inactivation and reactivation by UVC-LED. The study also highlights that adequate UVC-LED irradiation and avoidance of visible light after UVC-LED disinfection can effectively inhibit bacterial reactivation. Our findings form a reference for the design and operation of UV disinfection in aquaculture.

Deyeuxia angustifolia upward migration and nitrogen deposition change soil microbial community structure in an alpine tundra - Na Li; Haibo Du; Mai-He Li; Risu Na; Renkai Dong; Hong S. He; Shengwei Zong; Lirong Huang; Zhengfang Wu (Soil Biology and Biochemistry, 2023)

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

Rational design of molecular phototheranostic platform for NIR-II fluorescence imaging guided chemodynamic-photothermal combined therapy - Gui-long Wu; Bin Sun; Yuxuan He; Xiaofeng Tan; Qi Pan; Sha Yang; Na Li; Minghui Wang; Peixian Wu; Fen Liu; Hao Xiao; Li Tang; et al. (Chemical Engineering Journal, 2023)

Molecular characteristics and biological effects of dissolved organic matter leached from microplastics during sludge hydrothermal treatment - Jun Chen; Na Wan; Kewei Li; Hu Aibin; Hang He; Dongsheng Wang; Weijun Zhang (Journal of Hazardous Materials, 2023)

Robust cellulose-based hydrogel marbles with excellent stability for gas sensing - Na Li; Hongying Wanyan; Shengchang Lu; He Xiao; Min Zhang; Kai Liu; Xiuliang Li; Bihui Du; Liulian Huang; Lihui Chen; Yonghao Ni; Hui Wu (Carbohydrate Polymers, 2023)

Multiple roles of ferric chloride in preparing efficient magnetic hydrochar for sorption of methylene blue from water solutions - Xiao-Na Sun; Kun Yu; Jiong-Hua He; Yan Chen; Jian-Zhong Guo; Bing Li (Bioresource Technology, 2023)

[Cuproptosis-related immune gene signature predicts clinical benefits from anti-PD-1/PD-L1 therapy in non-small-cell lung cancer - Linfeng Luo; Anlin Li; Sha Fu; Wei Du; Li-Na He; Xuanye Zhang; Yixing Wang; Yixin Zhou; Yang Yunpeng; Zhang Li; Shaodong Hong (Immunologic Research, 2023)

Polarity-extended composition profiling via LC-MS-based metabolomics approaches: A key to functional investigation of Citrus aurantium L - Wen Miao; Xiaojing Liu; Na Li; Xiqing Bian; Yiran Zhao; Jing He; Tingting Zhou; Jian-Lin Wu (Food Chemistry, 2023)

Low expression of miR-1929-3p mediates murine cytomegalovirus-induced fibrosis in cardiac fibroblasts via targeting endothelin a receptor/NLRP3 inflammasome pathway - Jiayi Li; Yongjia Wang; LaMei Wang; Yuanyuan Qu; Wei Zhou; Hua Zhong; DongMei Xi; Na Tang; Fang He (In Vitro Cellular & Developmental Biology - Animal, 2023)

A review of advanced oxidation process towards organic pollutants and its potential application in fracturing flowback fluid - Xing Li; Yang Bai; Xian Shi; Shuang Chang; Shuting Tian; Meiming He; Na Su; Pingya Luo; Wanfen Pu; Zhicheng Pan (Environmental Science and Pollution Research, 2023)

A novel endophytic bacterial strain improves potato storage characteristics by degrading glycoalkaloids and regulating microbiota - Fei Song; Chen Li; Na Zhang; Xiaoyun He; Hongru Yang; Ziru Yan; Yangping Zhou; Hongtao Tian; Kunlun Huang (Postharvest Biology and Technology, 2023)

Construction of PP membranes with robust interfacial stability by ALD and fluorinated grafting for high salt solution distillation - Lei Zhang; Dan He; Jia Li; Yanting Li; Yiming Xiao; Jun Xiang; Wei Du; Na Tang (Desalination, 2023)

An integrative analysis of lncRNAs and mRNAs highlights the potential roles of lncRNAs in the process of follicle selection in Taihang chickens - Bei-Bei Zhang; Meng-Xiao Li; Hong-Na Wang; Chao Liu; Yan-Yan Sun; Teng-He Ma (Theriogenology, 2023)

Structural evolution of lignite from heterogeneous particles to homogeneous products during ruthenium ion catalytic oxidation depolymerization - Yinling Zhang; Huacong Zhou; Jianxiu Hao; Qiufeng Wang; Na Li; Runxia He; Keduan Zhi; Shukun Le; Quansheng Liu (Fuel, 2023)

Multimedia fates and ecological risk control strategies of phthalic acid esters in a lake recharged by reclaimed water using the QWASI fugacity model - Chenchen Wang; Jing Li; Chunsheng Qiu; Lei Wang; Xiao Su; Panpan Huang; Na He; Liping Sun; Yaohui Bai; Chaocan Li; Yufei Wang (Ecological Modelling, 2023)

Isochrysis sp. cultivation in pilot-scale to concurrently produce sustainable triacylglycerols for human milk fat substitutes and fucoxanthin - Daogui Li; Na Chen; Zhihua Zhou; Cairong Zhong; Jingping Fang; Luqiang Huang; Han Sun; Chengdeng Chi; Youcai Zhou; Yongjin He (Algal Research, 2023)

Aaptamine derivatives with CDK2 inhibitory activities from the South China Sea sponge Aaptos suberitoides - Qian-Qian He; Yu-Qing Man; Kun-Lai Sun; Li-Juan Yang; Yan Wu; Jing Du; Wei-Wei Chen; Juan-Juan Dai; Na Ni; Shuang Miao; Kai-Kai Gong (Natural Product Research, 2022)

Low-Level Environmental Per- and Polyfluoroalkyl Substances and Preterm Birth: A Nested Case–Control Study Among a Uyghur Population in Northwestern China - Bo-Yi Yang; Jianhua Wu; Xilong Niu; Chuanjiang He; Michael S. Bloom; Maihefuzaimu Abudoukade; Mairiyemu Abulizi; Aimin Xu; Beibei Li; Li Li; Xuemei Zhong; Qi-Zhen Wu; et al. (Exposure and Health, 2022)

Binding characteristics of Pb and Zn to low-temperature feces-based biochar-derived DOM revealed by EEM-PARAFAC combined with general and moving-window two-dimensional correlation analyses - Changjun He; Xuwen He; Run Yuan; Na Li; Jinyuan Jiang (Environmental Science and Pollution Research, 2022)

Evaluating the Response of a Tunnel Subjected to Strike-Slip Fault Rupture in Conjunction with Model Test and Hybrid Discrete–Continuous Numerical Modeling - Cui Zhen; Li Jian-he; Fu Xing-wei; Sheng Qian; Zhou Guang-xin; Ma Ya-li-na; Wang Tian-qiang (Rock Mechanics and Rock Engineering, 2022)

Anti-inflammatory and antioxidant activities of chemical constituents from the flower buds of Buddleja officinalis - Fei-Bing Huang; Na Liang; Nusrat Hussain; Xu-Dong Zhou; Muhammad Ismail; Qing-Ling Xie; Huang-He Yu; Yu-Qing Jian; Cai-Yun Peng; Bin Li; Bin Liu; Sheng-Huang Chen; et al. (Natural Product Research, 2022)

Selection of low-cadmium and high-micronutrient wheat cultivars and exploration of the relationship between agronomic traits and grain cadmium - Shuangshuang Li; Xianmin Huang; Na Liu; Yihui Chen; Huan He; Xiaoyu Cao; Jiulan Dai (Environmental Science and Pollution Research, 2022)

Correction: Interaction of declined handgrip strength and HIV infection on neurocognitive impairment - Shiying Yuan; Xiaoxiao Chen; Haijiang Lin; Ruizi Shi; Jing Li; Lulu Xu; Shijie Qiao; Yingying Ding; Na He (Journal of NeuroVirology, 2022)

Interaction of declined handgrip strength and HIV infection on neurocognitive impairment - Shiying Yuan; Xiaoxiao Chen; Haijiang Lin; Ruizi Shi; Jing Li; Lulu Xu; Shijie Qiao; Yingying Ding; Na He (Journal of NeuroVirology, 2022)

Comprehensive review on catalytic degradation of Cl-VOCs under the practical application conditions - Fawei Lin; Li Xiang; Zhiman Zhang; Na Li; BeiBei Yan; Chi He; Zhengping Hao; Guanyi Chen (Critical Reviews in Environmental Science and Technology, 2022)

Cancer metabolism and tumor microenvironment: fostering each other? - Yiyuan Yuan; Huimin Li; Wang Pu; Leilei Chen; Dong Guo; Hongfei Jiang; Bo He; Siyuan Qin; Kui Wang; Na Li; Jingwei Feng; Jing Wen; et al. (Science China Life Sciences, 2022)

Long non-coding RNA ILF3-AS1 facilitates hepatocellular carcinoma progression by stabilizing ILF3 mRNA in an m6A-dependent manner - Changwen Bo; Na Li; Li He; Sujing Zhang; Yonghui An (Human Cell, 2021)

Comparative Mucous miRomics in Cynoglossus semilaevis Related to Vibrio harveyi Caused Infection - Na Zhao; Lei Jia; Guangli Li; Xiaoxu He; Chunhua Zhu; Bo Zhang (Marine Biotechnology, 2021)

Sinanaerobacter chloroacetimidivorans gen. nov., sp. nov., an obligate anaerobic bacterium isolated from anaerobic sludge - Yixuan Bao; Junwei Liu; Xuan Zhang; Peng Lei; Jiguo Qiu; Jian He; Na Li (Antonie van Leeuwenhoek, 2021)

Genetic control and phenotypic characterization of panicle architecture and grain yield-related traits in foxtail millet (Setaria italica) - Hui Zhi; Qiang He; Sha Tang; Junjun Yang; Wei Zhang; Huifang Liu; Yanchao Jia; Guanqing Jia; Aiying Zhang; Yuhui Li; Erhu Guo; Ming Gao; et al. (Theoretical and Applied Genetics, 2021)

Bacillus megaterium strain WW1211 promotes plant growth and lateral root initiation via regulation of auxin biosynthesis and redistribution - Shengwang Wang; Xiaofan Na; Lei Yang; Cuifang Liang; Li He; Jie Jin; Ziyu Liu; Juan Qin; Junjie Li; Xiaomin Wang; Yurong Bi (Plant and Soil, 2021)

Circ_0001666 affects miR-620/WNK2 axis to inhibit breast cancer progression - Na Su; Li Liu; Shan He; Linghai Zeng (Genes & Genomics, 2021)

Tritonibacter aquimaris sp. nov. and Tritonibacter litoralis sp. nov., two novel members of the Roseobacter group isolated from coastal seawater - Na Li; Xiao-yan He; Ning-hua Liu; Tie-ji Gu; Jian Li; Yu-hui Geng; Shan Zhang; Peng Wang; Hui-hui Fu; Mei Shi; Xiu-lan Chen; Yu-zhong Zhang; et al. (Antonie van Leeuwenhoek, 2021)

Effects of different types of microbial inoculants on available nitrogen and phosphorus, soil microbial community, and wheat growth in high-P soil - Yihui Chen; Shuangshuang Li; Na Liu; Huan He; Xiaoyu Cao; Cheng Lv; Ke Zhang; Jiulan Dai (Environmental Science and Pollution Research, 2021)

Nocardioides acrostichi sp. nov., a novel endophytic actinobacterium isolated from leaf of Acrostichum aureum - Xiao-Hui Chen; Fei Li; Fei-Na Li; Ming-Sheng Chen; Xiao-Rui Yan; Zi-Bang He; Shun-Lian Li; You-Lang Wu; Li Tuo (Antonie van Leeuwenhoek, 2021)

Ocean surface current retrieval and imaging with a new shore-based X-band radar based on time-shifted up-and-down linear frequency modulated signal - Yijun He; Xin Song; Baochang Liu; Na Yi; Xiuzhong Li (Acta Oceanologica Sinica, 2021)

Variations of soil organic matters and plant cuticular waxes along an altitude gradient in Qinghai-Tibet Plateau - Luhua Yao; Na Guo; Yuji He; Yu Xiao; Yang Li; Jianhua Gao; Yanjun Guo (Plant and Soil, 2021)

Virtual screening of potentially endocrine-disrupting chemicals against nuclear receptors and its application to identify PPARγ-bound fatty acids - Chaitanya K. Jaladanki; Yang He; Li Na Zhao; Sebastian Maurer-Stroh; Lit-Hsin Loo; Haiwei Song; Hao Fan (Archives of Toxicology, 2021)
Nuclear receptors (NRs) are key regulators of energy homeostasis, body development, and sexual reproduction. Xenobiotics binding to NRs may disrupt natural hormonal systems and induce undesired adverse effects in the body. However, many chemicals of concerns have limited or no experimental data on their potential or lack-of-potential endocrine-disrupting effects. Here, we propose a virtual screening method based on molecular docking for predicting potential endocrine-disrupting chemicals (EDCs) that bind to NRs. For 12 NRs, we systematically analyzed how multiple crystal structures can be used to distinguish actives and inactives found in previous high-throughput experiments. Our method is based on (i) consensus docking scores from multiple structures at a single functional state (agonist-bound or antagonist-bound), (ii) multiple functional states (agonist-bound and antagonist-bound), and (iii) multiple pockets (orthosteric site and alternative sites) of these NRs. We found that the consensus enrichment from multiple structures is better than or comparable to the best enrichment from a single structure. The discriminating power of this consensus strategy was further enhanced by a chemical similarity-weighted scoring scheme, yielding better or comparable enrichment for all studied NRs. Applying this optimized method, we screened 252 fatty acids against peroxisome proliferator-activated receptor gamma (PPARγ) and successfully identified 3 previously unknown fatty acids with Kd = 100–250 μM including two furan fatty acids: furannonanoic acid (FNA) and furanundecanoic acid (FUA), and one cyclopropane fatty acid: phytomonic acid (PTA). These results suggested that the proposed method can be used to rapidly screen and prioritize potential EDCs for further experimental evaluations.

Image-Forming Visual Basis of Empathy for Pain in Mice - Kai-Wen Geng; Rui Du; Na Wei; Chun-Li Li; Yan Wang; Wei Sun; Tao Chen; Dong-Yu Wei; Yang Yu; Ting He; Wen-Jun Luo; Rui-Rui Wang; et al. (Neuroscience Bulletin, 2020)

Etv5 safeguards trophoblast stem cells differentiation from mouse EPSCs by regulating fibroblast growth factor receptor 2 - Kui Zhu; Yuan Liu; Chen Fan; Mengyao Zhang; Hongxia Cao; Xin He; Na Li; Dianfeng Chu; Fang Li; Min Zou; Jinlian Hua; Huayan Wang; et al. (Molecular Biology Reports, 2020)

Activation of p62-Keap1-Nrf2 Pathway Protects 6-Hydroxydopamine-Induced Ferroptosis in Dopaminergic Cells - Yiran Sun; Libo He; Taoyu Wang; Wan Hua; Huan Qin; Jingjin Wang; Li Wang; Wanqin Gu; Tingting Li; Na Li; Xinanbei Liu; Fang Chen; et al. (Molecular Neurobiology, 2020)

Cerebral Organoids Repair Ischemic Stroke Brain Injury - Shu-Na Wang; Zhi Wang; Tian-Ying Xu; Ming-He Cheng; Wen-Lin Li; Chao-Yu Miao (Translational Stroke Research, 2020)
Stroke is the second leading cause of death and main cause of disability worldwide, but with few effective therapies. Although stem cell-based therapy has been proposed as an exciting regenerative medicine strategy for brain injury, there are limitations. The developed cerebral organoids (COs) represent a promising transplantation source for stroke that remains to be answered. Here, we transplanted COs at 55 days and explored the feasibility in the rat middle cerebral artery occlusion (MCAO) model of stroke. COs transplantation at 6 h or even 24 h after MCAO significantly reduces brain infarct volume and improves neurological motor function. Transplanted COs show the potential of multilineage differentiation to mimic in vivo cortical development, support motor cortex region-specific reconstruction, form neurotransmitter-related neurons, and achieve synaptic connection with host brain via in situ differentiation and cell replacement in stroke. Cells from transplanted COs show extensive migration into different brain regions along corpus callosum. The mechanisms underlying COs transplantation therapy are also associated with enhanced neurogenesis, synaptic reconstruction, axonal regeneration and angiogenesis, and decreased neural apoptosis with more survival neurons after stroke. Moreover, COs transplantation promotes predominantly exogenous neurogenesis in the transplantation periphery of ipsilateral cortex and predominantly endogenous neurogenesis in the hippocampus and subventricular zone. Together, we demonstrate the efficacy and underlying mechanisms of COs transplantation in stroke. This preliminary but promising study provides first-hand preclinical evidence for COs transplantation as a potential and effective intervention for stroke treatment.

The utility of fusing multi-sensor data spatio-temporally in estimating grassland aboveground biomass in the three-river headwaters region of China - Na Zeng; Honglin He; Xiaoli Ren; Li Zhang; Yuan Zeng; Jiangwen Fan; Yuzhe Li; Zhongen Niu; Xiaobo Zhu; Qingqing Chang (International Journal of Remote Sensing, 2020)

Correction to: CCR2 and CCR5 promote diclofenac-induced hepatotoxicity in mice - Zhanke He; Guoquan Wei; Na Li; Mengwei Niu; Shenhai Gong; Guangyan Wu; Teng Wang; Yong Jiang; Peng Chen (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Production, Identification and Characterization of Erianthus rockii × Narenga porphyrocoma Intergeneric Hybrids as a New Germplasm for Sugarcane Breeding and Genetic Research - Hailong Chang; Qinnan Wang; Yongsheng Qiu; Yuanxia Qin; Xueting Li; Qingdan Wu; Weiping He; Yuqiang Guo; Wei Zhang; Junlv Chen; Na Fang (Sugar Tech, 2020)

Identification and characterization of the melanocortin 1 receptor gene (MC1R) in hypermelanistic Chinese tongue sole (Cynoglossus semilaevis) - Kunming Li; Na Zhao; Bo Zhang; Lei Jia; Kefeng Liu; Qunshan Wang; Xiaoxu He; Baolong Bao (Fish Physiology and Biochemistry, 2020)

Quantitative Trait Locus Mapping for Yield-Associated Agronomic Traits in a BC2F6 Population of Japonica Hybrid Rice Liaoyou 5218 - Zhibin Li; Zetian Hua; Li Dong; Wei Zhu; Guangsheng He; Lijun Qu; Na Qi; Zhengjin Xu; Fang Wang (Journal of Plant Growth Regulation, 2020)

Identification and validation of the superior alleles for wheat kernel traits detected by genome-wide association study under different nitrogen environments - Na Zhang; Xilan Zhang; Liqiang Song; Qiannan Su; Shuai Zhang; Jiajia Liu; Wei Zhang; Xiaoyi Fu; Minghui Zhao; Lijing Sun; Jun Ji; Wenchen Qiao; et al. (Euphytica, 2020)

Pedobacter indicus sp. nov., isolated from deep-sea sediment - Xiao-yan He; Na Li; Xiu-lan Chen; Yu-zhong Zhang; Xi-ying Zhang; Xiao-yan Song (Antonie van Leeuwenhoek, 2020)

A solvent-assisted active loading technology to prepare gambogic acid and all-trans retinoic acid co-encapsulated liposomes for synergistic anticancer therapy - Kexin Na; Kai Liu; Jiang Yu; Xue Wang; Meng Li; Chutong Tian; Haixia He; Yuan He; Yongjun Wang (Drug Delivery and Translational Research, 2020)

Elevated insulin levels compromise endometrial decidualization in mice with decrease in uterine apoptosis in early-stage pregnancy - Chen Zhang; Chengshun Yang; Na Li; Xueqing Liu; Junlin He; Xuemei Chen; Yubin Ding; Chao Tong; Chuan Peng; Hubin Yin; Yingxiong Wang; Rufei Gao (Archives of Toxicology, 2019)

rTMS combined with motor training changed the inter-hemispheric lateralization - Jing-na Jin; Xin Wang; Ying Li; He Wang; Zhi-peng Liu; Tao Yin (Experimental Brain Research, 2019)

Increased CXCL13 and CXCR5 in Anterior Cingulate Cortex Contributes to Neuropathic Pain-Related Conditioned Place Aversion - Xiao-Bo Wu; Li-Na He; Bao-Chun Jiang; Xue Wang; Ying Lu; Yong-Jing Gao (Neuroscience Bulletin, 2019)

MicroRNA-494 targets PTEN and suppresses PI3K/AKT pathway to alleviate hypertrophic scar formation - Ting He; Yue Zhang; Yang Liu; Hongtao Wang; Wanfu Zhang; Jiaqi Liu; Na Li; Yan Li; Luxu Wang; Songtao Xie; Dahai Hu (Journal of Molecular Histology, 2019)

Synergistic deletion of RGS1 and COS1 may reduce the pathogenicity of Magnaporthe oryzae - He Na; An Bang; Xie Qing-biao; Yan Xia; Feng Hui-min; Luo Hong-li; He Chao-zu (Archives of Microbiology, 2019)

Methane emissions responding to Azolla inoculation combined with midseason aeration and N fertilization in a double-rice cropping system - Ya-Dong Yang; He-Shui Xu; Deng-Yun Li; Jing-Na Liu; Jiang-Wen Nie; Zhao-Hai Zeng (Environmental Science and Pollution Research, 2019)

Seminal Plasma Exosomes: Promising Biomarkers for Identification of Male and Pseudo-Males in Cynoglossus semilaevis - Bo Zhang; Na Zhao; Lei Jia; Kang Peng; Jinyuan Che; Kunming Li; Xiaoxu He; Jinsheng Sun; Baolong Bao (Marine Biotechnology, 2019)

OsCDC48/48E complex is required for plant survival in rice (Oryza sativa L.) - Lei Shi; Xiao-bo Zhang; Yong-feng Shi; Xia Xu; Yuqing He; Guosheng Shao; Qi-na Huang; Jian-li Wu (Plant Molecular Biology, 2019)

CCR2 and CCR5 promote diclofenac-induced hepatotoxicity in mice - Zhanke He; Guoquan Wei; Na Li; Mengwei Niu; Shenhai Gong; Guangyan Wu; Teng Wang; Yong Jiang; Peng Chen (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

Purification of the total steroidal saponins from fenugreek seeds ( Trigonella foenum - graecum L.) using aqueous two-phase system and determination of diosgenin content using micellar electrokinetic chromatography method - Na Wang; Famei He; Wenliang Li; Xu Fang; Hailing Li (Natural Product Research, 2019)

Complete genome analysis of a novel phage GW1 lysing Cronobacter - Haiyan Zeng; Wenjing He; Chengsi Li; Jumei Zhang; Na Ling; Yu Ding; Liang Xue; Moutong Chen; Haoming Wu; Qingping Wu (Archives of Virology, 2019)

Regimes of rainfall preceding regional rainfall events over the plain of Beijing City - Weihua Yuan; Hang Xu; Rucong Yu; Jian Li; Yingxin Zhang; Na He (International Journal of Climatology, 2018)
Four regimes of rainfall that preceded strong regional rainfall events (RREs) over the plain area of Beijing City (BJP) were studied using hourly station‐based rainfall observations during the warm season (May–October) of the past 8 years. The RREs were outlined by the maximum rainfall at all stations over the BJP each hour. The strong RREs were classified into four groups based on the rainfall that occurred in the 3 hr before the start of the events, which originated from areas northwest, southeast, northeast and southwest of the BJP. The four groups of RREs exhibited different characteristics. The number of RREs from the northwestern mountains was the highest, that is, approximately twice (four times) that from the northeastern mountains and the southwestern plain (southeastern coastal areas). The amounts, intensities and durations of the RREs from the southwestern plain were two to fourfold higher than those from the three other directions. The mean rainfall centres of the RREs from the northeast and southeast were located outside the BJP. Correspondingly, the spatial coverages and homogeneities of the RREs in the BJP from the northeast and southeast were poorer than those from the two other directions. All four groups of RREs ended to the southeast of the BJP and occurred mainly from the late afternoon to the early morning. Detailed rainfall classification based on the origination and feature analyses of all rainfall processes will enrich our knowledge of the rainfall evolutions of the BJP. In addition, combined with a study of the circulation of the rainfall processes, comprehensive understanding of fine‐scale rainfall features will provide further information for rainfall forecasting. In the future, our analyses will be applied to the corresponding atmospheric circulations of those RREs with different origins to identify the key factors that lead to different rainfall distributions.

Biodegradation of Pendimethalin by Paracoccus sp. P13 - Haiyan Ni; Na Li; Jiguo Qiu; Qing Chen; Jian He (Current Microbiology, 2018)

Description of a new species of Triplophysa (Teleostei: Nemacheilidae) from Guizhou Province, China - Wei‐Jun Wu; An‐You He; Jun‐Xing Yang; Li‐Na Du (Journal of Fish Biology, 2018)
A new cave‐dwelling fish species Triplophysa guizhouensis is described based on specimens collected from Guizhou, China, in a subterranean system interconnected with the Hongshui River drainage. The species can be distinguished from its congeners by a combination of characters: eyes present; caudal fin with 14 branched rays; inner gill rakers of first gill arch 8–10; posterior chamber of air bladder developed; and body posterior of dorsal fin scaled. A key to species of Triplophysa in the Pearl River basin is provided.

Both widespread PEP‐CTERM proteins and exopolysaccharides are required for floc formation of Zoogloea resiniphila and other activated sludge bacteria - Na Gao; Ming Xia; Jingcheng Dai; Dianzhen Yu; Weixing An; Shuyang Li; Shuangyuan Liu; Penghui He; Liping Zhang; Zhenbin Wu; Xuezhi Bi; Shouwen Chen; et al. (Environmental Microbiology, 2018)
Summary Bacterial floc formation plays a central role in the activated sludge (AS) process, which has been widely utilized for sewage and wastewater treatment. The formation of AS flocs has long been known to require exopolysaccharide biosynthesis. This study demonstrates an additional requirement for a PEP‐CTERM protein in Zoogloea resiniphila , a dominant AS bacterium harboring a large exopolysaccharide biosynthesis gene cluster. Two members of a wide‐spread family of high copy number‐per‐genome PEP‐CTERM genes, transcriptionally regulated by the RpoN sigma factor and accessory PrsK‐PrsR two‐component system and at least one of these, pepA , must be expressed for Zoogloea to build the floc structures that allow gravitational sludge settling and recycling. Without PrsK or PrsR, Zoogloea cells were planktonic rather than flocculated and secreted exopolysaccharides were released into the growth broth in soluble form. Overexpression of PepA could circumvent the requirement of rpoN , prsK and prsR for the floc‐forming phenotype by fixing the exopolysaccharides to bacterial cells. However, overexpression of PepA, which underwent post‐translational modifications, could not rescue the long‐rod morphology of the rpoN mutant. Consistently, PEP‐CTERM genes and exopolysaccharide biosynthesis gene cluster are present in the genome of the floc‐forming Nitrospira comammox and Mitsuaria strain as well as many other AS bacteria.

Methylation of secreted frizzled-related protein 1 (SFRP1) promoter downregulates Wnt/β-catenin activity in keloids - Jiaqi Liu; Huayu Zhu; Hongtao Wang; Jun Li; Fu Han; Yang Liu; Wanfu Zhang; Ting He; Na Li; Zhao Zheng; Dahai Hu (Journal of Molecular Histology, 2018)

An Optimized and Feasible Preparation Technique for the Industrial Production of Hydrogel Patches - Wei-Ze Li; Wen-Xia Han; Xu-Liang Hao; Ning Zhao; Xi-Feng Zhai; Li-Bin Yang; Shu-Miao He; Yu-Chuan Cheng; Han Zhang; Li-Na Fu; Yan Zhang; Ze Liang (AAPS PharmSciTech, 2018)

Impact of IL-10-1082A/G gene polymorphism on the severity of EV71 infection in Chinese children - Qiubo Li; Hongfang He; Ya Guo; Yu Zhang; Peipei Liu; Yedan Liu; Chengqing Yang; Jie Song; Na Zhang; Zongbo Chen (Archives of Virology, 2018)

A new catechin derivative from the fruits of Rosa sterilis S. D. Shi - Xu-Lu Luo; Han-Long Dan; Na Li; Yong-He Li; Ying-Jun Zhang; Ping Zhao (Natural Product Research, 2017)

Ion Channel Genes and Epilepsy: Functional Alteration, Pathogenic Potential, and Mechanism of Epilepsy - Feng Wei; Li-Min Yan; Tao Su; Na He; Zhi-Jian Lin; Jie Wang; Yi-Wu Shi; Yong-Hong Yi; Wei-Ping Liao (Neuroscience Bulletin, 2017)

Transcriptional sequencing and analysis of major genes involved in the adventitious root formation of mango cotyledon segments - Yun-He Li; Hong-Na Zhang; Qing-Song Wu; Gloria K. Muday (Planta, 2017)

A Point Mutation in SCN1A 5′ Genomic Region Decreases the Promoter Activity and Is Associated with Mild Epilepsy and Seizure Aggravation Induced by Antiepileptic Drug - Qu-Wen Gao; Li-Dong Hua; Jie Wang; Cui-Xia Fan; Wei-Yi Deng; Bin Li; Wen-Jun Bian; Chuan-Xing Shao; Na He; Peng Zhou; Wei-Ping Liao; Yi-Wu Shi (Molecular Neurobiology, 2017)

“Turn-Off-On” Fluorescence Switching of Ascorbic Acid-Reductive Silver Nanoclusters: a Sensor for Ascorbic Acid and Arginine in Biological Fluids - Na Li; Yu He; Yili Ge; Gongwu Song (Journal of Fluorescence, 2017)

Isolation, identification and genomic characterization of the Asian lineage Zika virus imported to China - Yong-Qiang Deng; Hui Zhao; Xiao-Feng Li; Na-Na Zhang; Zhong-Yu Liu; Tao Jiang; Da-Yong Gu; Lei Shi; Jian-An He; Hong-Jiang Wang; Zhao-Zeng Sun; Qing Ye; et al. (Science China Life Sciences, 2016)

Eimeria tenella: a novel dsRNA virus in E. tenella and its complete genome sequence analysis - Bin Wu; Xichen Zhang; Pengtao Gong; Mingying Li; He Ding; Caiyan Xin; Na Zhao; Jianhua Li (Virus Genes, 2016)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

HPLC simultaneous determination of arbutin, chlorogenic acid and 6′- O -caffeoylarbutin in different parts of Vaccinium dunalianum Wight - Xu-Lu Luo; Na Li; Min Xu; Hong-Tao Zhu; Peng He; Yong Ding; Ping Zhao; Ying-Jun Zhang (Natural Product Research, 2015)

Knockdown of PFTK1 Inhibits the Migration of Glioma Cells - Shaochen Fan; Chengjin Zhao; Li Zhang; Shirong Dai; Jianbing Ren; Xiubing Zhang; Na Ban; Xiaojuan He; Lixiang Yang; Zhen Bao; Wenjuan Chen; Jie Sun; et al. (Journal of Molecular Neuroscience, 2015)

Geographic and genetic identification of RppS, a novel locus conferring broad resistance to southern corn rust disease in China - Xiaojun Wu; Na Li; Panfeng Zhao; Yan He; Shoucai Wang (Euphytica, 2015)

Rapid emergence of a PB2-E627K substitution confers a virulent phenotype to an H9N2 avian influenza virus during adaption in mice - Xiaoyu Sang; Airong Wang; Tongjie Chai; Xijun He; Jie Ding; Xiaolong Gao; Yuanguo Li; Kun Zhang; Zhiguang Ren; Lin Li; Zhijun Yu; Tiecheng Wang; et al. (Archives of Virology, 2015)

Deep water distribution and transport in the Nordic seas from climatological hydrological data - Yan He; Jinping Zhao; Na Liu; Zexun Wei; Yahao Liu; Xiang Li (Acta Oceanologica Sinica, 2015)

The genus Codonopsis (Campanulaceae): a review of phytochemistry, bioactivity and quality control - Jing-Yu He; Na Ma; Shu Zhu; Katsuko Komatsu; Zhi-Yuan Li; Wei-Ming Fu (Journal of Natural Medicines, 2015)
Codonopsis , in the family Campanulaceae, is a genus containing 42 species of dicotyledonous herbaceous perennial plants, predominantly found in Central, East and South Asia. Several Codonopsis species are widely used in traditional medicine and are considered to have multiple medicinal properties. Among the Codonopsis species, Codonopsis pilosula (Franch.) Nannf. and C. lanceolata (Sieb. et Zucc.) Benth. & Hook. f. ex Trautv. are more popular than others according to the findings, especially phytochemical and bioactive studies. Phytochemical research shows that Codonopsis species contain mainly polyacetylenes, phenylpropanoids, alkaloids, triterpenoids and polysaccharides, which contribute to multiple bioactivities. However, the mechanisms of their bioactivities need to be further elucidated. The less popular Codonopsis species remain to be studied and exploited. In addition, although a series of methods for the quality evaluation of Codonopsis species have been developed, a feasible and reliable approach to the efficacious and safe use of various Codonopsis species is still needed, with considering botanical origin, chemical constituents and bioactive effects. This review aims to provide up-to-date and comprehensive information on the phytochemistry, bioactivity and quality control of medicinal plants in the genus Codonopsis and to highlight current gaps in knowledge, which is useful for the wider development of the Codonopsis genus.

Lipopolysaccharides Upregulate Hepcidin in Neuron via Microglia and the IL-6/STAT3 Signaling Pathway - Zhong-Ming Qian; Xuan He; Tuo Liang; Ka-Chun Wu; Yik-Chun Yan; Li-Na Lu; Guang Yang; Qian Qian Luo; Wing-Ho Yung; Ya Ke (Molecular Neurobiology, 2014)

Erratum to: Overexpression of Human E46K Mutant α-Synuclein Impairs Macroautophagy via Inactivation of JNK1-Bcl-2 Pathway - Jia-Qing Yan; Yu-He Yuan; Yan-Na Gao; Ju-Yang Huang; Kai-Li Ma; Yan Gao; Wan-Qing Zhang; Xiao-Feng Guo; Nai-Hong Chen (Molecular Neurobiology, 2014)

Overexpression of Human E46K Mutant α-Synuclein Impairs Macroautophagy via Inactivation of JNK1-Bcl-2 Pathway - Jia-Qing Yan; Yu-He Yuan; Yan-Na Gao; Ju-Yang Huang; Kai-Li Ma; Yan Gao; Wan-Qing Zhang; Xiao-Feng Guo; Nai-Hong Chen (Molecular Neurobiology, 2014)

Needle-free injection of insulin powder: delivery efficiency and skin irritation assessment - Chun-yu Li; Zhe-wei Wang; Can Tu; Jia-bo Wang; Bing-qian Jiang; Qi Li; Ling-na Zeng; Zhi-jie Ma; Ping Zhang; Yan-ling Zhao; Ya-ming Zhang; Dan Yan; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

A novel method for the rapid detection of benzo(a)pyrene in liquid milk by dimethyl sulfoxide selectively enhanced synchronous fluorescence spectrometry - Li-Rong Lin; He-Dong Luo; Xiu-Ying Li; Na Li; Na Zhou; Yu-Zhu Jia; Yi-Hong Liu; Yao-Qun Li (Food Additives & Contaminants: Part A, 2014)

Long-term activity of earthquake-induced landslides: A case study from Qionghai Lake Basin, Southwest of China - Xue-li Wei; Ning-sheng Chen; Qian-gong Cheng; Na He; Ming-feng Deng; Javed Iqbal Tanoli (Journal of Mountain Science, 2014)

Molecular phylogeny and genetic variation in the genus Lilium native to China based on the internal transcribed spacer sequences of nuclear ribosomal DNA - Yun-peng Du; Heng-bin He; Zhong-xuan Wang; Shuang Li; Chi Wei; Xiao-na Yuan; Qi Cui; Gui-xia Jia (Journal of Plant Research, 2014)

Genetic variation at 8q24, family history of cancer, and upper gastrointestinal cancers in a Chinese population - Heather P. Tarleton; Shen-Chih Chang; Sungshim Lani Park; Lin Cai; Baoguo Ding; Na He; Shehnaz K. Hussain; Qingwu Jiang; Li-Na Mu; Jianyu Rao; Hua Wang; Nai-Chieh Y. You; et al. (Familial Cancer, 2014)

Molecular characterization of a duck Tembusu virus from China - XiaoFei Bai; Rang Lv; ChunGuo Liu; Na Qiu; Yilong He; XiuChen Yin; XiaoJun Li; Ming Liu; Yun Zhang (Virus Genes, 2013)

Genes encoding the production of extracellular polysaccharide bioflocculant are clustered on a 30-kb DNA segment in Bacillus licheniformis - Shan Yan; Na Wang; Zhen Chen; Yuanpeng Wang; Ning He; Yajuan Peng; Qingbiao Li; Xu Deng (Functional & Integrative Genomics, 2013)

Advances in monoclonal antibody application in myocarditis - Li-na Han; Shuang He; Yu-tang Wang; Li-ming Yang; Si-yu Liu; Ting Zhang (Journal of Zhejiang University-SCIENCE B, 2013)

CD73+ adipose-derived mesenchymal stem cells possess higher potential to differentiate into cardiomyocytes in vitro - Qiong Li; Li-Jie Qi; Zhi-Kun Guo; He Li; Hong-Bo Zuo; Na-Na Li (Journal of Molecular Histology, 2013)

ATP Regulates Sodium Channel Kinetics in Pancreatic Islet Beta Cells - Na Zou; Xiao Wu; Yan-Yan Jin; Meng-Zao He; Xin-Xin Wang; Li-Da Su; Marjan Rupnik; Zhen-Yong Wu; Li Liang; Ying Shen (The Journal of Membrane Biology, 2013)

Isolation and Characterization of the Cold-Induced Phyllostachys edulis AP2/ERF Family Transcription Factor, peDREB1 - Lei Liu; Xiao-Lu Cao; Rui Bai; Na Yao; Lu-Bin Li; Cong-Fen He (Plant Molecular Biology Reporter, 2012)

Molecular cloning, characterization expression of P450c17-I and P450c17-II and their functions analysis during the reproductive cycle in males of barfin flounder (Verasper moseri) - Guo X. Jin; Hai S. Wen; Feng He; Ji F. Li; Cai F. Chen; Jia R. Zhang; Xiao Y. Chen; Bao Shi; Dan Shi; Yan P. Yang; Bao X. Qi; Na Li (Fish Physiology and Biochemistry, 2012)

Perfluoroalkyl compounds in municipal WWTPs in Tianjin, China—concentrations, distribution and mass flow - Hongwen Sun; Xianzhong Zhang; Lei Wang; Tao Zhang; Fasong Li; Na He; Alfredo C. Alder (Environmental Science and Pollution Research, 2012)

Down-regulation of β3-integrin inhibits bone metastasis of small cell lung cancer - Na Li; Jian-ping Zhang; Shan Guo; Jie Min; Li–li Liu; Hai-chuan Su; Ying-ming Feng; He-long Zhang (Molecular Biology Reports, 2012)

The mechanism of mimecan transcription induced by glucocorticoid in pituitary corticotroph cells - Xiao Na Zhang; Li Qiong Xue; He Jiang; Shao Ying Yang; Huai Dong Song; Qin Yun Ma (Molecular and Cellular Biochemistry, 2012)

Trace analysis of persistent toxic substances in the main stream of Jiangsu section of the Yangtze River, China - Huan He; Guan-jiu Hu; Cheng Sun; Su-lan Chen; Ming-na Yang; Juan Li; Yong Zhao; Hui Wang (Environmental Science and Pollution Research, 2011)

Molecular characterization and expression analysis of elongation factors 1A and 2 from the Pacific white shrimp, Litopenaeus vannamei - Lei Wang; Yuan Liu; Wei-Na Wang; Wei-Jun Mai; Yu Xin; Jun Zhou; Wen-Yin He; An-Li Wang; Ru-Yong Sun (Molecular Biology Reports, 2011)

Cloning and expression of P450c17-I (17α-hydroxylase/17,20-lyase) in brain and ovary during gonad development in Cynoglossus semilaevis - Cai F. Chen; Hai S. Wen; Zhao P. Wang; Feng He; Jia R. Zhang; Xiao Y. Chen; Guo X. Jin; Bao Shi; Dan Shi; Yan P. Yang; Ji F. Li; Bao X. Qi; et al. (Fish Physiology and Biochemistry, 2010)

Design, expression and characterization of recombinant hybrid peptide Attacin-Thanatin in Escherichia coli - Li Na Wang; Bing Yu; Guo Quan Han; Jun He; Dai Wen Chen (Molecular Biology Reports, 2010)

Sevoflurane postconditioning reduces myocardial reperfusion injury in rat isolated hearts via activation of PI3K/Akt signaling and modulation of Bcl-2 family proteins - Li-na Yu; Jing Yu; Feng-jiang Zhang; Mei-juan Yang; Ting-ting Ding; Jun-kuan Wang; Wei He; Tao Fang; Gang Chen; Min Yan (Journal of Zhejiang University-SCIENCE B, 2010)

Genetic evolution of equine influenza viruses isolated in China - Ting Qi; Wei Guo; Wen-Qiang Huang; Hong-Mei Li; Li-Ping Zhao; Ling-Li Dai; Na He; Xiao-Fang Hao; Wen-Hua Xiang (Archives of Virology, 2010)

Species and distribution of rare earth elements in the Baotou section of the Yellow River in China - Jiang He; Chang-Wei Lü; Hong-Xi Xue; Ying Liang; Saruli Bai; Ying Sun; Li-Li Shen; Na Mi; Qing-Yun Fan (Environmental Geochemistry and Health, 2010)

Extended expression of B-class MADS-box genes in the paleoherb Asarum caudigerum - Yin-He Zhao; Michael Möller; Jun-Bo Yang; Ting-Song Liu; Jin-Feng Zhao; Li-Na Dong; Jin-Peng Zhang; Cheng-Yun Li; Guo-Ying Wang; De-Zhu Li (Planta, 2010)

Identification and characterization of a novel ∆6-fatty acid desaturase gene from Rhizopus nigricans - He Lu; Jia-Na Li; You-Rong Chai; Xue-Kun Zhang (Molecular Biology Reports, 2009)

Differential Expression of Serine/Threonine Protein Phosphatase Type-2C Under Drought Stress in Maize - Fu-Hua Li; Feng-Ling Fu; Li-Na Sha; Liang He; Wan-Chen Li (Plant Molecular Biology Reporter, 2009)

Genome-wide association scan for stature in Chinese: evidence for ethnic specific loci - Shu-Feng Lei; Tie-Lin Yang; Li-Jun Tan; Xiang-Ding Chen; Yan Guo; Yan-Fang Guo; Liang Zhang; Xiao-Gang Liu; Han Yan; Feng Pan; Zhi-Xin Zhang; Yu-Mei Peng; et al. (Human Genetics, 2009)

Association study of the oestrogen signalling pathway genes in relation to age at natural menopause - Li-Na He; Dong-Hai Xiong; Yong-Jun Liu; Feng Zhang; Robert R. Recker; Hong-Wen Deng (Journal of Genetics, 2007)

Association of MTHFR C677T and SHMT1 C1420T with susceptibility to ESCC and GCA in a high incident region of Northern China - Yimin Wang; Wei Guo; Yutong He; Zhifeng Chen; Denggui Wen; Xiufeng Zhang; Na Wang; Yan Li; Hui Ge; Jianhui Zhang (Cancer Causes & Control, 2007)

Bone marrow mesenchymal stem cell transplantation combined with perindopril treatment attenuates infarction remodelling in a rat model of acute myocardial infarction - Jian-an Wang; Rong-hua Luo; Xing Zhang; Xiao-jie Xie; Xin-yang Hu; Ai-na He; Jie Chen; Jia-hui Li (Journal of Zhejiang University-SCIENCE B, 2006)